Hydrogenated conjugated diene copolymer, resin composition, cured product, resin film, prepreg, laminate, and printed wiring board
A hydrogenated conjugated diene copolymer with a random structure and specific properties is used to enhance the dielectric performance and tensile strength of resin compositions for printed circuit boards, addressing the limitations of existing materials.
Patent Information
- Application Number
- CN202380039304.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-18
- Filing Date
- 2023-05-17
- Publication Date
- 2024-12-20
AI Technical Summary
Existing resin compositions for printed circuit boards and flexible circuit boards have insufficient dielectric constants and dielectric loss tangents, and the addition of modifiers often reduces tensile strength, limiting information capacity and processing speed.
A hydrogenated conjugated diene copolymer with a random structure, specific molecular weight, and hydrogenation rate, combined with polar resins, to form a resin composition that achieves low dielectric constant and loss tangent with improved tensile strength.
The hydrogenated conjugated diene copolymer composition results in a cured product with low dielectric constant and loss tangent, along with enhanced tensile strength, suitable for high-performance electronic devices.
Smart Images

Figure BDA0005125057160000421 
Figure BDA0005125057160000501 
Figure BDA0005125057160000511
Abstract
Description
Technical Field
[0001] The present invention relates to a hydrogenated conjugated diene copolymer, a resin composition, a cured product, a resin film, a prepreg, a laminate, and a printed wiring board. Background Art
[0002] In recent years, with the remarkable progress of information network technology and the expansion of services using information networks, electronic devices are required to achieve larger information capacity and higher processing speed.
[0003] In order to meet these needs, materials with low dielectric loss are being sought for various substrate materials such as printed circuit boards and flexible circuit boards.
[0004] Conventionally, in order to obtain materials with low dielectric loss, research and publication have been conducted on cured resins having as main components thermosetting resins such as epoxy resins and thermoplastic resins such as polyphenylene ether resins which have low dielectric constants and low dielectric loss tangents and excellent mechanical properties such as strength.
[0005] However, the materials disclosed in the past still have room for improvement in terms of low dielectric constant and low dielectric loss tangent, and have a problem that the amount of information and the processing speed are limited when they are used in printed circuit boards.
[0006] In order to improve this problem, various rubber components have been proposed as modifiers for the above-mentioned thermosetting resins and thermoplastic resins.
[0007] For example, Patent Document 1 discloses, as a modifier for achieving low dielectric loss tangent and low dielectric constant of polyphenylene ether resin, at least one elastomer selected from the group consisting of copolymers of vinyl aromatic compounds and olefin-based olefin compounds and hydrogenated products thereof, and homopolymers of vinyl aromatic compounds.
[0008] In addition, Patent Document 2 discloses a styrene-based elastomer as a modifier for lowering the dielectric loss tangent and the dielectric constant of an epoxy resin.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2021-147486
[0012] Patent Document 2: Japanese Patent Application Publication No. 2020-15861 Summary of the invention
[0013] Problems to be solved by the invention
[0014] However, the cured products of the resin compositions using the modifiers disclosed in Patent Documents 1 and 2 still have insufficient lowering of dielectric constant and dielectric loss tangent, and have problems in that the tensile strength is reduced due to the addition of the modifier, and sufficient strength cannot be obtained.
[0015] Therefore, an object of the present invention is to provide a hydrogenated conjugated diene copolymer which can provide a cured product having a low dielectric constant and a low dielectric loss tangent and excellent tensile strength, and a resin composition containing the hydrogenated conjugated diene copolymer.
[0016] Means of solving problems
[0017] The present inventors have conducted intensive studies to solve the above-mentioned problems of the prior art and have found that a cured product of a resin composition containing a hydrogenated conjugated diene copolymer having a predetermined structure has a low dielectric constant and a low dielectric loss tangent and is also excellent in strength characteristics, thereby completing the present invention.
[0018] That is, the present invention is as follows. [1]
[0020] A hydrogenated conjugated diene copolymer, wherein:
[0021] The copolymer is a random copolymer having vinyl aromatic monomer units and conjugated diene monomer units.
[0022] The random copolymer is hydrogenated.
[0023] The weight average molecular weight of the random copolymer is 35,000 or less. [2]
[0025] The hydrogenated conjugated diene copolymer as described in the above [1], wherein the hydrogenation rate of the hydrogenated conjugated diene copolymer is 5 to 95%. [3]
[0027] The hydrogenated conjugated diene copolymer as described in the above [1], wherein
[0028] The conjugated diene copolymer before hydrogenation of the hydrogenated conjugated diene copolymer comprises a unit (a) derived from a 1,2-bond and / or a 3,4-bond, and a unit (b) derived from a 1,4-bond.
[0029] When the total content of the conjugated diene monomer units is 100%, the content of the units (a) derived from 1,2-bonds and / or 3,4-bonds is 80% or less. [4]
[0031] The hydrogenated conjugated diene copolymer as described in [2] above, wherein
[0032] The conjugated diene copolymer before hydrogenation of the hydrogenated conjugated diene copolymer comprises a unit (a) derived from a 1,2-bond and / or a 3,4-bond, and a unit (b) derived from a 1,4-bond.
[0033] When the total content of the conjugated diene monomer units is 100%, the content of the units (a) derived from 1,2-bonds and / or 3,4-bonds is 80% or less. [5]
[0035] The hydrogenated conjugated diene-based copolymer according to any one of the above [1] to [4], wherein the hydrogenation rate of the hydrogenated conjugated diene-based copolymer is 15 to 85%. [6]
[0037] The hydrogenated conjugated diene-based copolymer according to any one of the above [1] to [5], wherein the content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene-based copolymer is 35 to 75% by mass. [7]
[0039] A resin composition comprising:
[0040] Component (I): the hydrogenated conjugated diene copolymer described in any one of [1] to [6] above; and
[0041] At least one component selected from the group consisting of the following components (II) to (IV).
[0042] Component (II): Free radical initiator
[0043] Component (III): Polar resin (excluding component (I))
[0044] Component (IV): Curing agent (excluding component (II)) [8]
[0046] The resin composition as described in the above-mentioned [7], wherein
[0047] The resin composition contains the above-mentioned component (III),
[0048] The component (III) is at least one selected from the group consisting of epoxy resins, polyimide resins, polyphenylene ether resins, liquid crystal polyester resins, and fluorine resins. [9]
[0050] The resin composition as described in the above-mentioned [7], wherein
[0051] The component (III) is at least one polar resin selected from the group consisting of epoxy resins, polyimide resins and polyphenylene ether resins.
[0052] The component (I) is the hydrogenated conjugated diene copolymer described in [6].
[10]
[0054] The resin composition according to any one of [7] to [9] above, wherein the component (III) is an epoxy resin.
[11]
[0056] A cured product comprising the conjugated diene copolymer according to any one of [1] to [6] above.
[12]
[0058] A cured product, which is a cured product of the resin composition according to any one of [7] to
[10] above.
[13]
[0060] A resin film comprising the resin composition according to any one of [7] to
[10] above.
[14]
[0062] A prepreg comprising a composite of a substrate and the resin composition according to any one of [7] to
[10] above.
[15]
[0064] The prepreg as described in the above-mentioned
[14] , wherein the above-mentioned base material is glass cloth.
[16]
[0066] A laminate comprising the resin film described in
[13] above and a metal foil.
[17]
[0068] A laminate comprising a cured product of the prepreg according to
[14] or
[15] above, and a metal foil.
[18]
[0070] A printed wiring board comprising the cured product described in
[12] above.
[0071] Effects of the Invention
[0072] According to the present invention, there are provided a hydrogenated conjugated diene copolymer which can provide a cured product having a low dielectric constant and a low dielectric loss tangent and excellent in tensile strength, and a resin composition containing the hydrogenated conjugated diene copolymer. DETAILED DESCRIPTION
[0073] A specific embodiment of the present invention (hereinafter referred to as “this embodiment”) will be described in detail below.
[0074] It should be noted that the following embodiments are examples for explaining the present invention and are not intended to limit the present invention to the following contents. The present invention can be implemented with various modifications within the scope of the gist.
[0075] [Hydrogenated conjugated diene copolymer]
[0076] The hydrogenated conjugated diene-based copolymer of the present embodiment is a random polymer having a vinyl aromatic monomer unit and a conjugated diene monomer unit. The random copolymer is hydrogenated and has a weight average molecular weight of 35,000 or less.
[0077] According to the hydrogenated conjugated diene-based copolymer of the present embodiment, a cured product having a low dielectric constant and a low dielectric loss tangent and excellent strength characteristics can be obtained.
[0078] The conjugated diene monomer unit refers to a structural unit derived from a conjugated diene compound in a polymer formed by polymerizing the conjugated diene compound.
[0079] The conjugated diene compound is a diene having one pair of conjugated double bonds.
[0080] Examples of the conjugated diene compound include, but are not limited to, 1,3-butadiene, 2-methyl-1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, and 1,3-cyclohexadiene.
[0081] Among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred. 1,3-Butadiene and isoprene are widely used, easily available, and advantageous from the viewpoint of cost, and can be easily copolymerized with styrene which is widely used as a vinyl aromatic compound described later.
[0082] These substances may be used alone or in combination of two or more.
[0083] The conjugated diene compound may be a compound obtained by biotechnology.
[0084] The vinyl aromatic monomer unit refers to a structural unit derived from a vinyl aromatic compound in a polymer formed by polymerizing the vinyl aromatic compound.
[0085] Examples of the vinyl aromatic compound include, but are not limited to, styrene, α-methylstyrene, p-methylstyrene, divinylbenzene, 1,1-diphenylethylene, N,N-dimethyl-p-aminoethylstyrene, and N,N-diethyl-p-aminoethylstyrene.
[0086] These substances may be used alone or in combination of two or more.
[0087] (Random copolymer)
[0088] The hydrogenated conjugated diene copolymer of the present embodiment is a random copolymer having a vinyl aromatic monomer unit and a conjugated diene monomer unit. It is preferred that no monomer other than the vinyl aromatic compound and the conjugated diene compound be added to the hydrogenated conjugated diene copolymer of the present embodiment.
[0089] Regarding the distribution state of the vinyl aromatic monomer units in the hydrogenated conjugated diene copolymer, the vinyl aromatic monomer units in the hydrogenated conjugated diene copolymer can be uniformly distributed or can be distributed in a tapered shape. In addition, the part where the vinyl aromatic monomer units are uniformly distributed and / or the part where they are distributed in a tapered shape can exist in plural numbers, but preferably there is no block consisting only of the vinyl aromatic monomer units.
[0090] Since the polymerization rates of vinyl aromatic compounds and conjugated diene compounds are different, even if the polymerization is carried out in a state where both are contained in the system, depending on the polymerization conditions, the following situation may occur: the conjugated diene compound is consumed first, and the proportion of the vinyl aromatic compound increases in the second half, thereby forming a block of vinyl aromatic monomer units.
[0091] A preferred mode in the production process of the hydrogenated conjugated diene polymer of the present embodiment is to set the conditions such as adding a randomizer or adjusting the polymerization temperature in such a manner that such a block of vinyl aromatic monomer units is not formed. However, if the hydrogenated conjugated diene copolymer as a whole is regarded as a random copolymer, a state in which blocks of vinyl aromatic monomer units and / or conjugated diene monomer units are partially formed is not excluded.
[0092] Regarding the above-mentioned embodiment regarded as a random copolymer, specifically, it refers to an embodiment in which the polymer portion composed only of vinyl aromatic monomer units is less than 15% by mass, preferably less than 13% by mass, more preferably less than 10% by mass, further preferably less than 7% by mass, further more preferably less than 5% by mass, further preferably less than 4% by mass, and particularly preferably less than 3% by mass, relative to the total amount of vinyl aromatic monomer units constituting the hydrogenated conjugated diene copolymer of the present embodiment.
[0093] By making the amount of the polymer portion formed only by the vinyl aromatic monomer units less than 15% by mass of the total amount of the vinyl aromatic monomer units, the hydrogenated conjugated diene copolymer of the present embodiment can be specifically distinguished from the block copolymer having a polymer block structure having vinyl aromatic monomer units and conjugated diene monomer units as structural units, and has good compatibility with the components (II), (III) and (IV) described later, thereby obtaining excellent strength and dielectric properties.
[0094] The content of each monomer unit constituting the hydrogenated conjugated diene copolymer of the present embodiment can be measured by a method using a nuclear magnetic resonance apparatus (NMR) (the method described in Y. Tanaka, et al., RUBBER CHEMISTRY and TECHNOLOGY 54, 685 (1981), hereinafter referred to as “NMR method”) using the hydrogenated conjugated diene copolymer of the present embodiment as an analyte.
[0095] As described below, the resin composition of the present embodiment includes the hydrogenated conjugated diene copolymer of the present embodiment (component (I)), component (II): a radical initiator, component (III): a polar resin, and component (IV): a curing agent.
[0096] Component (II), component (III) and component (IV) described below have a polar group.
[0097] From the aspect of solubility parameter, the compatibility of vinyl aromatic compound and composition (II), composition (III) and composition (IV) tends to be higher than conjugated diene compound, in the hydrogenated conjugated diene copolymer of the present embodiment, by copolymerization with vinyl aromatic compound, the polarity of polymer chain as a whole increases. As a result, by being the random copolymer of vinyl aromatic monomer unit and conjugated diene monomer unit, the compatibility with composition (III) and composition (IV) is further improved, and the strength of the resin combination and cured product of the present embodiment described later is improved.
[0098] The conjugated diene compound has free radical reactivity. As described above, the random copolymer has excellent compatibility with component (II), component (III) and component (IV). Therefore, the conjugated diene monomer unit in the random copolymer is present in a position close to component (II), component (III) and component (IV), and the conjugated diene monomer unit is in a state where it is easy for the reaction to occur with these components.
[0099] In addition, by improving the compatibility of the above-mentioned random copolymer and composition (II), composition (III) and composition (IV), the mobility reduction and polarization of the polymer caused by the external electric field can be suppressed in the resin combination and cured product of the present embodiment described later, and the low dielectric loss tangent and low dielectric constant of the resin combination and cured product tend to improve. The loss (dielectric constant) caused by the polarization of the polymer due to the external electric field, the energy loss (dielectric loss tangent) caused by the heat generated by movement can be suppressed by fully ensuring the compatibility and reactivity with the composition (III) and composition (IV) described later. Therefore, when the hydrogenated conjugated diene copolymer of the present embodiment is a copolymer containing the above-mentioned vinyl aromatic monomer unit and conjugated diene monomer unit, the strength of the resin combination and cured product of the present embodiment can be improved, and it is made to have low dielectric loss tangent and low dielectric constant.
[0100] From the perspective of improving the strength of the above-mentioned cured product, as well as reducing the dielectric loss tangent and the dielectric constant, the content of monomer units other than the vinyl aromatic monomer unit and the conjugated diene monomer unit in the hydrogenated conjugated diene polymer of this embodiment is preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 10% by mass or less, and further more preferably 0% by mass (without intentionally adding other monomers).
[0101] (hydrogenation)
[0102] The hydrogenated conjugated diene-based copolymer of the present embodiment is a copolymer obtained by reacting hydrogen with a conjugated diene monomer unit, that is, a copolymer that has been hydrogenated.
[0103] By hydrogenation, the polarity of the conjugated diene copolymer is reduced, and the loss (dielectric constant) caused by the polarization of the polymer due to the external electric field and the energy loss (dielectric loss tangent) generated by the movement of heat may be reduced, so the resin composition and cured product containing the hydrogenated conjugated diene copolymer of this embodiment tend to achieve low dielectric loss tangent and low dielectric constant. That is, in the structure of the hydrogenated conjugated diene monomer unit having a random structure of the conjugated diene monomer unit and the vinyl aromatic monomer unit, the random structure can ensure compatibility with other components (the random structure is dominant compared to the hydrogenation rate), and the hydrogenated structure can reduce the polarity from the perspective of dielectric performance, forming a design with excellent characteristic balance.
[0104] In the hydrogenated conjugated diene copolymer of the present embodiment, the unsaturated bonds from the conjugated diene compound are hydrogenated from the aspects of reactivity with the above-mentioned other components and dielectric properties. The hydrogenation rate is preferably 5% or more, more preferably 10% or more, further preferably 15% or more, further more preferably 20% or more, further more preferably 30% or more, and particularly preferably 35% or more. From the aspect of fully ensuring the reactivity with the above-mentioned other components, the upper limit of the hydrogenation rate is preferably 95% or less, more preferably 94% or less, further preferably 93% or less, further more preferably 92% or less, further preferably 91% or less, particularly preferably 90% or less, and most preferably 85% or less.
[0105] In the resin composition of the present embodiment described later, a conjugated diene copolymer that is not hydrogenated may also be used in combination within the range that does not impair the above-mentioned dielectric properties and strength, but from the aspect of the above-mentioned dielectric properties and strength, the content of the conjugated diene copolymer that is not hydrogenated in the resin composition of the present embodiment is preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 10% by mass or less, further more preferably 5% by mass or less, and further preferably 0% by mass in the resin composition. In the case of 0% by mass, a conjugated diene copolymer having a weight average molecular weight greater than 35,000 is not contained.
[0106] In addition, as described above, the hydrogenation rate of the hydrogenated conjugated diene polymer of this embodiment is particularly preferably 15% or more, more preferably 20% or more, and further preferably 25% or more. From the aspects of the above-mentioned reactivity and dielectric properties, the upper limit is preferably 85% or less, more preferably 80% or less, and further preferably 75% or less.
[0107] If the hydrogenation rate of the hydrogenated conjugated diene polymer is 15% or more, the dielectric properties of the hydrogenated conjugated diene copolymer are good, and the resin composition and cured product of the present embodiment tend to have excellent dielectric properties. If the hydrogenation rate of the hydrogenated conjugated diene polymer is 85% or less, the reactivity with component (III): polar resin and the reactivity of the hydrogenated conjugated diene copolymers with each other can be fully ensured, and the resin composition and cured product of the present embodiment tend to have excellent toughness.
[0108] The method for hydrogenating the conjugated diene copolymer is not particularly limited, and a known method can be applied.
[0109] When performing the hydrogenation reaction, a known hydrogenation catalyst can be used. Examples of hydrogenation catalysts include: (1) supported heterogeneous hydrogenation catalysts in which metals such as Ni, Pt, Pd, and Ru are supported on carbon, silicon oxide, aluminum oxide, diatomaceous earth, and the like; (2) so-called Ziegler-type hydrogenation catalysts using organic acid salts or transition metal salts such as acetylacetonate of Ni, Co, Fe, and Cr and reducing agents such as organic aluminum; (3) homogeneous hydrogenation catalysts such as so-called organic metal complexes such as organic metal compounds of Ti, Ru, Rh, and Zr.
[0110] As the hydrogenation catalyst, specifically, those described in JP-B-42-8704, JP-B-43-6636, JP-B-63-4841, JP-B-1-37970, JP-B-1-53851, and JP-B-2-9041 can be used.
[0111] Preferred hydrogenation catalysts include cyclopentadienyl titanium compounds and reducing organic metal compounds.
[0112] As the cyclopentadienyl titanium compound, the compounds described in Japanese Patent Publication No. 8-109219 can be used. As the cyclopentadienyl titanium compound, for example, biscyclopentadienyl titanium dichloride, mono(pentamethylcyclopentadienyl)titanium trichloride and the like can be cited but are not limited to compounds having at least one ligand having a substituted or unsubstituted cyclopentadienyl skeleton, an indenyl skeleton or a fluorenyl skeleton. In the cyclopentadienyl titanium compound, the above skeletons may include one alone or two in combination.
[0113] Examples of the reducing organometallic compound include, but are not limited to, organoalkali metal compounds such as organolithium, organomagnesium compounds, organoaluminum compounds, organoboron compounds, and organozinc compounds.
[0114] These may be used alone or in combination of two or more.
[0115] The hydrogenation rate of the hydrogenated conjugated diene-based copolymer of the present embodiment can be controlled within the above numerical range by adjusting the reaction temperature, reaction time, hydrogen supply amount, catalyst amount, and the like in the hydrogenation method.
[0116] The reaction temperature during hydrogenation is preferably 55 to 200° C., more preferably 60 to 170° C., and even more preferably 65 to 160° C. In addition, the pressure of hydrogen used in the hydrogenation reaction is preferably 0.1 to 15 MPa, more preferably 0.2 to 10 MPa, and even more preferably 0.3 to 5 MPa. In addition, the reaction time is usually 3 minutes to 10 hours, and preferably 10 minutes to 5 hours.
[0117] The hydrogenation reaction may be carried out in a batch process, a continuous process, or a combination thereof.
[0118] (Weight average molecular weight (Mw))
[0119] The weight average molecular weight (Mw) of the hydrogenated conjugated diene-based copolymer of the present embodiment is 35,000 or less.
[0120] The weight average molecular weight can be measured by the method described in the examples described later, and is obtained as follows: based on a calibration curve obtained by measurement based on commercially available standard polystyrene (made using the peak molecular weight of standard polystyrene), the peak molecular weight of a chromatogram obtained by measurement based on gel permeation chromatography (hereinafter sometimes referred to as GPC) is obtained, thereby obtaining the weight average molecular weight.
[0121] Molecular weight distribution is the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn).
[0122] From the perspective of preventing deterioration in handling properties due to mixing of a low molecular weight polymer described below, the molecular weight distribution of a single peak of the conjugated diene copolymer of the present embodiment measured by GPC is preferably 5.0 or less, more preferably 4.0 or less, further preferably 3.0 or less, and further more preferably 2.5 or less.
[0123] By making the weight average molecular weight of the hydrogenated conjugated diene copolymer of the present embodiment less than 35,000, the crosslinking property is improved, a uniform mesh structure is formed, and a high-strength cured product is obtained. In addition, the compatibility with the component (III) and component (IV) described later is improved, and the resin composition and cured product of the present embodiment tend to achieve low dielectric constant and low dielectric loss tangent.
[0124] In addition, when the resin composition of the present embodiment is used to form a prepreg, when the varnish described later is impregnated in a substrate such as glass cloth described later, by making the weight average molecular weight of the hydrogenated conjugated diene copolymer of the present embodiment less than 35,000, the hydrogenated conjugated diene copolymers are uniformly cross-linked with each other and are uniformly compatible with the component (III): polar resin described later, thereby improving the strength of the cured product containing the hydrogenated conjugated diene copolymer, and there is a tendency to achieve low dielectric loss tangent and low dielectric constant.
[0125] In addition, in the prepreg, the permeability into the base material is improved, a uniform prepreg can be produced, the strength can be improved, and there is a tendency that a low dielectric loss tangent and a low dielectric constant can be achieved.
[0126] The weight average molecular weight of the hydrogenated conjugated diene copolymer of the present embodiment is 35,000 or less, preferably 30,000 or less, more preferably 25,000 or less, further preferably 20,000 or less, and further more preferably 15,000 or less. The lower limit of the weight average molecular weight of the hydrogenated conjugated diene copolymer is not particularly limited, but is preferably 500 or more from the perspective of suppressing the stickiness of the hydrogenated conjugated diene copolymer and achieving good handling properties.
[0127] As mentioned above, in the resin combination of the present embodiment, can share the conjugated diene copolymer with weight average molecular weight greater than 35,000 in the scope of not damaging dielectric properties and intensity, but if weight average molecular weight is greater than 35,000, then the storage stability under the varnish state described later tends to deteriorate. It is believed that this is because, if the weight average molecular weight of conjugated diene copolymer is large, then the cohesive force of conjugated diene copolymer increases each other, and easily dissolves in varnish. Particularly under the situation of using high polar resins such as epoxy resin, polyimide resin as component (III) described later, because the polarity of conjugated diene copolymer is lower than the resin of these components (III), therefore the cohesion of conjugated diene copolymer each other is promoted, and the deterioration of the storage stability with resin combination becomes significant tendency.
[0128] From the above aspects, in the resin composition of the present embodiment, the content of the conjugated diene copolymer having a weight average molecular weight greater than 35,000 in the resin composition components is preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 10% by mass or less, further more preferably 5% by mass or less, and further preferably 0% by mass or less.
[0129] In addition, if the hydrogenated conjugated diene copolymers react excessively with each other, they will be in an over-crosslinked state, and the toughness will tend to decrease. If the weight average molecular weight of the hydrogenated conjugated diene polymer is large, it is easy to be in the above-mentioned over-crosslinked state, and the toughness will tend to decrease. From this aspect, the weight average molecular weight of the hydrogenated conjugated diene copolymer of the present embodiment is 35,000 or less, preferably 30,000 or less, more preferably 25,000 or less, further preferably 20,000 or less, and further more preferably 15,000 or less.
[0130] The weight average molecular weight and molecular weight distribution of the hydrogenated conjugated diene copolymer of the present embodiment can be controlled within the above numerical range by adjusting polymerization conditions such as the amount of monomers added, the timing of addition, the polymerization temperature, and the polymerization time in the polymerization step.
[0131] (Content of vinyl aromatic monomer units)
[0132] As mentioned above, in recent years, with the demand for miniaturization of various electronic devices, miniaturization is required for printed circuit boards. In order to miniaturize printed circuit boards, precise wiring is required, but in this case, the material used for printed wiring boards has a tendency to require more excellent toughness. Relative to the free radical initiator of component (II) described later and the rigid polar resin of component (III), the softer conjugated diene copolymer is dispersed and reacted to form a cross-linked structure, thereby the toughness of the cured product of the resin composition of the present embodiment described later tends to improve.
[0133] Generally, as component (III): polar resin, polyimide resin, epoxy resin, polyphenylene ether resin, etc. can be used, but when such resin is used, since these resins have higher polarity than component (I): hydrogenated conjugated diene copolymer, from the above viewpoint, in order to obtain better toughness, in order to improve dispersibility and reactivity, it is preferred that component (I): hydrogenated conjugated diene copolymer also has high polarity. That is, component (I): hydrogenated conjugated diene copolymer preferably has a high content of vinyl aromatic monomer units and a low hydrogenation rate.
[0134] On the other hand, the dielectric properties of hydrogenated conjugated diene copolymers with a high content of vinyl aromatic monomer units and a low hydrogenation rate are low, and the dielectric properties of the cured product of the resin composition of the present embodiment described later also tend to decrease. Therefore, by designing the content of the vinyl aromatic monomer units in the component (I): hydrogenated conjugated diene copolymer and the hydrogenation rate to an appropriate range, the balance of dispersibility, reactivity and dielectric properties of the hydrogenated conjugated diene copolymer can be controlled, and there is a tendency to obtain a resin composition and a cured product with excellent toughness and dielectric properties.
[0135] From the above viewpoint, the content of the vinyl aromatic monomer unit of the hydrogenated conjugated diene copolymer of the present embodiment is preferably 35 mass % or more, more preferably 40 mass % or more, and further preferably 45 mass % or more. From the aspect of the above-mentioned reactivity and dielectric performance, the upper limit is preferably 75 mass % or less, more preferably 70 mass % or less, and further preferably 65 mass % or less.
[0136] If the content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene copolymer of the present embodiment is 35% by mass or more, the dispersibility with component (III): polar resin is good, and there is a tendency to obtain excellent toughness. If the content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene copolymer is 75% by mass or less, the reactivity with component (III): polar resin and the reactivity of the hydrogenated conjugated diene copolymers can be fully ensured, the dielectric properties of the hydrogenated conjugated diene copolymer become excellent, and there is a tendency to obtain excellent toughness and dielectric properties in the resin composition and cured product of the present embodiment described later.
[0137] The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene-based copolymer of the present embodiment can be measured by NMR, and specifically, can be measured by the method described in Examples below.
[0138] The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene-based copolymer of the present embodiment can be controlled within the above numerical range by adjusting the amount of monomer added in the polymerization step.
[0139] (Vinyl bond amount)
[0140] Regarding the hydrogenated conjugated diene copolymer of the present embodiment, in the conjugated diene copolymer before hydrogenation, the conjugated diene monomer unit includes a unit (a) derived from a 1,2-bond and / or a 3,4-bond (hereinafter sometimes referred to as a unit (a)), and a unit (b) derived from a 1,4-bond (hereinafter sometimes referred to as a unit (b)). When the total content of the conjugated diene monomer units in the conjugated diene copolymer before hydrogenation is set to 100%, from the perspective of the storage stability of the varnish using the resin composition of the present embodiment, the content of the unit (a) derived from a 1,2-bond and / or a 3,4-bond (vinyl bond amount) is preferably 80% or less, more preferably 75% or less, and further preferably 70% or less. The lower limit is not particularly limited, but from the perspective of the reactivity of the conjugated diene monomer unit, it is preferably 5% or more, more preferably 10% or more, further preferably 15% or more, further more preferably 20% or more, further preferably 25% or more, and particularly preferably 30% or more.
[0141] The content of the unit (a) can be controlled within the above numerical range by using a regulator such as a polar compound in the polymerization step of the conjugated diene copolymer, and can be measured by the method described in the examples below.
[0142] Examples of the adjuster include tertiary amine compounds and ether compounds, and preferably, tertiary amine compounds are used.
[0143] The tertiary amine compound is a compound of the general formula: R1R2R3N (wherein R1, R2, and R3 are a hydrocarbon group having 1 to 20 carbon atoms, or a hydrocarbon group having a tertiary amino group).
[0144] Examples of tertiary amine compounds include, but are not limited to, trimethylamine, triethylamine, tributylamine, N,N-dimethylaniline, N-ethylpiperidine, N-methylpyrrolidine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, 1,2-dipiperidinylethane, trimethylaminoethylpiperazine, N,N,N',N",N"-pentamethylethylenetriamine, and N,N'-dioctyl-p-phenylenediamine.
[0145] The amount of the adjusting agent added is preferably 0.1 mol or more, more preferably 0.5 mol or more, and even more preferably 1.0 mol or more, relative to 1 mol of the polymerization initiator described below.
[0146] [Method for producing hydrogenated conjugated diene copolymer]
[0147] The hydrogenated conjugated diene-based copolymer of the present embodiment can be produced, for example, by performing living anionic polymerization using a polymerization initiator such as an organic alkali metal compound in a hydrocarbon solvent, followed by a hydrogenation reaction.
[0148] Examples of hydrocarbon solvents include, but are not limited to, aliphatic hydrocarbons such as n-butane, isobutane, n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclohexane, cycloheptane, and methylcycloheptane; aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene; and the like.
[0149] Examples of the polymerization initiator include organic alkali metal compounds such as aliphatic hydrocarbon alkali metal compounds, aromatic hydrocarbon alkali metal compounds, and organic amino alkali metal compounds, which are generally known to have anionic polymerization activity for conjugated diene compounds and vinyl aromatic compounds. Examples of the alkali metal include lithium, sodium, and potassium.
[0150] Examples of the organic alkali metal compound include aliphatic and aromatic hydrocarbon lithium compounds having 1 to 20 carbon atoms, including compounds containing one lithium in one molecule, and dilithium compounds, trilithium compounds, and tetralithium compounds containing a plurality of lithiums in one molecule.
[0151] Specific examples of the organic alkali metal compound include n-propyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, n-pentyl lithium, n-hexyl lithium, benzyl lithium, phenyl lithium, tolyl lithium, a reaction product of diisopropenylbenzene and sec-butyl lithium, and a reaction product of divinylbenzene, sec-butyl lithium and a small amount of 1,3-butadiene. In addition, 1-(tert-butoxy)propyl lithium disclosed in U.S. Patent No. 5,708,092 and a lithium compound in which one to several molecules of isoprene monomer are inserted to improve its solubility, alkyl lithium containing silyl groups such as 1-(tert-butyldimethylsilyloxy)hexyl lithium disclosed in British Patent No. 2,241,239, alkyl lithium containing amino groups disclosed in U.S. Patent No. 5,527,753, lithium diisopropylamine, and lithium amides such as lithium hexamethyldisilazide can also be used.
[0152] As for the method of polymerizing the vinyl aromatic compound and the conjugated diene compound using an organic alkali metal compound as a polymerization initiator, a conventionally known method can be applied.
[0153] The polymerization method may be, for example, batch polymerization, continuous polymerization, or a combination thereof. In particular, batch polymerization is suitable for obtaining a uniform polymer.
[0154] The polymerization temperature is preferably 0°C to 180°C, more preferably 30°C to 150°C.
[0155] The polymerization time varies depending on the conditions, but is usually within 48 hours, preferably 0.1 to 10 hours.
[0156] In addition, as the atmosphere of the polymerization system, an inert gas atmosphere such as nitrogen is preferred.
[0157] The polymerization pressure is not particularly limited as long as it is set to a pressure range that can maintain the monomer and the solvent in the liquid phase within the above temperature range. In addition, care must be taken not to allow impurities such as water, oxygen, and carbon dioxide, which deactivate the catalyst and active polymer, to enter the polymerization system.
[0158] Furthermore, at the end of the polymerization step, a necessary amount of a bifunctional or higher functional coupling agent may be added to conduct a coupling reaction. The coupling rate is preferably 40% or less, more preferably 30% or less, further preferably 20% or less, and further preferably no coupling agent is contained.
[0159] As the bifunctional coupling agent, conventionally known ones can be used without particular limitation.
[0160] Examples of the bifunctional coupling agent include alkoxysilane compounds such as trimethoxysilane, triethoxysilane, tetramethoxysilane, tetraethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane, dichlorodimethoxysilane, dichlorodiethoxysilane, trichloromethoxysilane, and trichloroethoxysilane; dihalides such as dichloroethane, dibromoethane, dimethyldichlorosilane, and dimethyldibromosilane; and acid esters such as methyl benzoate, ethyl benzoate, phenyl benzoate, and phthalates.
[0161] As the trifunctional or higher multifunctional coupling agent, conventionally known coupling agents can be used without particular limitation.
[0162] As the multifunctional coupling agent having three or more functions, for example, there can be mentioned polyols having three or more valences; polycyclic epoxy compounds such as epoxidized soybean oil, diglycidyl bisphenol A, 1,3-bis(N-N'-diglycidylaminomethyl)cyclohexane; n (wherein R represents a hydrocarbon group having 1 to 20 carbon atoms, X represents a halogen, and n represents an integer of 3 to 4) a halogenated silicon compound, such as methyltrichlorosilane, tert-butyltrichlorosilane, silicon tetrachloride, and bromides thereof; general formula R4-nSnX n(herein, R represents a hydrocarbon group having 1 to 20 carbon atoms, X represents a halogen, and n represents an integer of 3 to 4) a tin halide compound represented by, for example, polyvalent halides such as methyltin trichloride, tert-butyltin trichloride, and tin tetrachloride. In addition, dimethyl carbonate, diethyl carbonate, etc. may also be used.
[0163] As described above, the hydrogenation reaction of the conjugated diene copolymer can be carried out by a known method using a known hydrogenation catalyst.
[0164] The solution of the hydrogenated conjugated diene-based copolymer of the present embodiment obtained as described above can be separated from the solution by removing catalyst residues as necessary.
[0165] The compounds containing metal atoms in the polymerization initiator and the hydrogenation catalyst in the hydrogenation reaction when the hydrogenated conjugated diene copolymer is produced by anionic living polymerization react with moisture in the air in the desolvation process, etc. to generate a predetermined metal compound, which tends to remain in the hydrogenated conjugated diene copolymer. If these compounds are contained in the cured product, the dielectric constant and the dielectric loss tangent tend to increase, and further, ion migration tends to occur easily in the electronic material application.
[0166] As the metal compound left, the compound of the metal contained in the polymerization initiator and the hydrogenation catalyst can be cited, such as titanium oxide, amorphous titanium oxide, orthotitanic acid, metatitanic acid, titanium hydroxide, nickel hydroxide, nickel monoxide, lithium oxide, lithium hydroxide, cobalt oxide, cobalt hydroxide and other atoms containing oxides, lithium titanate, barium titanate, strontium titanate, nickel titanate, nickel-iron oxide and other atoms and heterogeneous metal composite oxides. From the perspective of realizing low dielectric constant, low dielectric loss tangent and not easy to produce ion migration in the cured product of the present embodiment, the residual amount of the metal compound in the conjugated diene copolymer of the present embodiment is preferably less than 150ppm, more preferably less than 130ppm, further preferably less than 100ppm, and further more preferably less than 90ppm in terms of residual metal amount. As specific residual metals, Ti, Ni, Li, Co and the like can usually be cited.
[0167] As a method for reducing the amount of residual metal in the hydrogenated conjugated diene copolymer of the present embodiment, a known method can be applied without particular limitation. For example, the following methods can be used: a method of adding water and carbon dioxide after the hydrogenation reaction of the conjugated diene copolymer to neutralize the hydrogenation catalyst residue; a method of adding an acid in addition to water and carbon dioxide to neutralize the hydrogenation catalyst residue. Specifically, the method described in Japanese Patent Application No. 2014-557427 can be applied.
[0168] Even when these metal removal methods are used, water containing the hydroxide of the metal compound is mixed in the desolvation step of the hydrogenated conjugated diene copolymer, so the hydroxide generally contains about 1 to 15 ppm. Therefore, it is preferred to remove 20% or more of the amount of metal added to the hydrogenated conjugated diene copolymer, more preferably 30% or more, further preferably 40% or more, further more preferably 50% or more, and further preferably 60% or more.
[0169] In addition, by reducing the added polymerization initiator and hydrogenation catalyst amount itself, the residual metal amount in the hydrogenated conjugated diene copolymer of the present embodiment can also be reduced, but if the polymerization initiator amount is reduced, the molecular weight of the hydrogenated conjugated diene copolymer increases, and if it is outside the above-mentioned preferred molecular weight range, the strength of the cured product tends to decrease. In addition, when carrying out the hydrogenation reaction, if the hydrogenation catalyst amount is reduced, the long-term hydrogenation reaction time and the high-temperature hydrogenation reaction temperature will be produced, and there is a tendency that the productivity significantly decreases.
[0170] As the solvent separation method for taking out the hydrogenated conjugated diene copolymer, for example, the following methods can be cited: a method in which acetone or alcohol is added to the reaction liquid after hydrogenation as a polar solvent that is a poor solvent for the hydrogenated conjugated diene copolymer to precipitate the hydrogenated conjugated diene copolymer and recover it; a method in which the reaction liquid is poured into hot water under stirring and the solvent is removed by steam stripping to recover it; a method in which the copolymer solution is directly heated to remove the solvent by distillation; and the like.
[0171] In addition, stabilizers such as various phenol stabilizers, phosphorus stabilizers, sulfur stabilizers, and amine stabilizers may be added to the hydrogenated conjugated diene copolymer.
[0172] In the production process of the hydrogenated conjugated diene-based copolymer of the present embodiment, the step of forming the “polar group” can be performed within a range that does not impair the dielectric properties.
[0173] Examples of polar groups include, but are not limited to, atomic groups containing at least one functional group selected from the group consisting of hydroxyl, carboxyl, carbonyl, thiocarbonyl, acyl halide, anhydride, carboxylic acid, thiocarboxylic acid, aldehyde, thialdehyde, carboxylate, amide, sulfonic acid, sulfonate, phosphoric acid, phosphate, amino, imino, nitrile, pyridyl, quinolyl, epoxy, thioepoxy, thioether, isocyanate, isothiocyanate, silicon halide, silanol, alkoxysilyl, tin halide, boric acid, boron-containing, borate, alkoxytin and phenyltin groups.
[0174] The polar group can be formed by reacting a modifier with the conjugated diene copolymer.
[0175] Examples of the modifier include, but are not limited to, tetraglycidyl-m-xylylenediamine, tetraglycidyl-1,3-bisaminomethylcyclohexane, ε-caprolactone, δ-valerolactone, 4-methoxybenzophenone, γ-glycidoxyethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyldimethylphenoxysilane, bis(γ-glycidoxypropyl)methylpropoxysilane, 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, N,N'-dimethylpropyleneurea, N-methylpyrrolidone, maleic acid, maleic anhydride, maleic anhydride imide, fumaric acid, itaconic acid, acrylic acid, methacrylic acid, glycidyl methacrylate, and crotonic acid.
[0176] As a method for forming a polar group, a known method can be applied without particular limitation.
[0177] For example, a melt-kneading method, a method in which each component is dissolved or dispersed and mixed in a solvent or the like to be reacted, and the like are mentioned.
[0178] In addition to the above-mentioned method of using a modifying agent, a method of using a polymerization initiator having a functional group and an unsaturated monomer having a functional group to perform polymerization by anionic living polymerization can also be applied.
[0179] Furthermore, the following methods can be cited: a method of modifying the copolymer by forming a functional group at the active end of the conjugated diene copolymer or by subjecting the copolymer to an addition reaction with a modifier containing a functional group; a method of reacting an organic alkali metal compound such as an organic lithium compound with the copolymer (metallization reaction) or subjecting the polymer to an addition reaction with a modifier having a functional group and an organic alkali metal added thereto.
[0180] [Resin composition]
[0181] The resin composition of the present embodiment contains the hydrogenated conjugated diene-based copolymer of the present embodiment (component (I)) and at least one component selected from the group consisting of the following components (II) to (IV).
[0182] Component (II): Free radical initiator
[0183] Component (III): Polar resin (excluding component (I))
[0184] Component (IV): Curing agent (excluding component (II))
[0185] From the perspective of lowering the dielectric constant, lowering the dielectric loss tangent, and improving flexibility of the resin composition of this embodiment and its cured product, the resin composition of this embodiment preferably contains component (I): a hydrogenated conjugated diene copolymer and component (II): a radical initiator.
[0186] (Component (II): free radical initiator)
[0187] As the radical initiator, a conventionally known radical initiator can be used, and examples thereof include a thermal radical initiator.
[0188] Examples of the thermal radical initiator include, but are not limited to, hydroperoxides such as diisopropylbenzene hydroperoxide (Percumyl P), cumene hydroperoxide (Percumyl H), and tert-butyl hydroperoxide (Perbutyl H); dialkyl peroxides such as α,α-bis(tert-butylperoxy-m-isopropyl)benzene (Perbutyl P), dicumyl peroxide (Percumyl D), 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (Perhexa 25B), tert-butylcumyl peroxide (Perbutyl C), di-tert-butyl peroxide (Perbutyl D), 2,5-dimethyl-2,5-bis(tert-butylperoxy)-3-hexyne (Perhexyne 25B), and tert-butyl peroxy(2-ethylhexanoate) (Perbutyl O); ketone peroxides; n-butyl-4,4-di(tert-butylperoxy)valerate (PERHEXA V) and other peroxide ketals; diacyl peroxides; peroxydicarbonates; organic peroxides such as peroxyesters; azo compounds such as 2,2-azobisisobutylnitrile, 1,1'-(cyclohexane-1-carbonitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), etc.
[0189] These initiators may be used alone or in combination of two or more.
[0190] (Component (III): polar resin)
[0191] In the resin composition of the present embodiment, from the aspect of imparting properties such as adhesion to a predetermined substrate, it is preferred to contain component (III): polar resin (excluding component (I)) within a range that does not impair the dielectric properties of the cured product. By containing the polar resin, the resin composition of the present embodiment tends to have excellent adhesion to a predetermined substrate.
[0192] When the component (III) is a polar resin having radical reactivity, the amount of the radical initiator of the component (II) may be adjusted as appropriate according to the reactivity, or the component (II) may not be added.
[0193] Regarding the polar resin with free radical reactivity as component (III), for example, a homopolymer of a compound having at least one vinyl group and / or a halogen element in the polymer, a copolymer of the above-mentioned compound having a vinyl group and / or a halogen element and any other compound can be cited. From the aspect of the dielectric properties of the resin composition and the cured product of this embodiment, a polymer having a vinyl group is preferred.
[0194] The above-mentioned polymer having a vinyl group may be a polymer composed of repeating units having a vinyl group, may be a polymer with a compound having a vinyl group and a polar group, or may be a polymer having a vinyl group obtained by reacting polar groups of a compound having a polar group.
[0195] Examples of the compound having a vinyl group and a polar group include, but are not limited to, (meth)acrylic acid (in the present invention, "(meth)acrylic acid" means methacrylic acid or acrylic acid), carboxyl group-containing vinyl monomers such as maleic acid, monoalkyl maleate, and fumaric acid, sulfonic group-containing vinyl monomers such as vinyl sulfonic acid, (meth)allyl sulfonic acid, methyl vinyl sulfonic acid, and styrene sulfonic acid, hydroxystyrene, N-hydroxymethyl (meth)acrylamide, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, phosphate group-containing vinyl monomers such as 2-hydroxyethyl (meth)acryloyl phosphate, 2-acryloyloxyethylphenyl phosphate, and 2-acryloyloxyethylphosphonic acid, hydroxystyrene, A vinyl monomer containing a hydroxyl group such as N-hydroxymethyl (meth)acrylamide, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, polyethylene glycol (meth)acrylate, 1-butene-3-ol, a vinyl monomer containing an amino group such as aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, a vinyl monomer containing an amide group such as (meth)acrylamide, N-methyl (meth)acrylamide, N-butylacrylamide, a vinyl monomer containing a nitrile group such as (meth)acrylonitrile, cyanostyrene, cyanoacrylate, a vinyl monomer containing an epoxy group such as glycidyl methacrylate, tetrahydrofurfuryl (meth)acrylate, p-vinylphenylphenyl oxide, etc.
[0196] Examples of the compound having a halogen element include, but are not limited to, vinyl chloride, vinyl bromide, vinylidene chloride, allyl chloride, chlorostyrene, bromostyrene, dichlorostyrene, chloromethylstyrene, tetrafluorostyrene, and chloroprene.
[0197] (Component (IV): curing agent)
[0198] When the radical reactivity of the component (III) is low, the resin composition of the present embodiment preferably contains a component (IV): a curing agent (excluding the component (II)) from the viewpoint of reactivity.
[0199] The component (IV): a curing agent generally has a function of reacting with the component (III): a polar resin to cure the resin composition.
[0200] "Reaction" between component (III) and component (IV) means that the polar groups of the respective components have covalent bonding properties. When polar groups react with each other, for example, when the OH of a carboxyl group is detached, the original polar group changes or disappears, but when a covalent bond is formed therefrom, it is included in the definition that the polar groups show "reactivity" with each other.
[0201] From the viewpoint of curing function, the curing agent as component (IV) preferably has at least two polar groups that can react with the functional groups of the polar resin as component (III) in one molecular chain.
[0202] The component (IV) may be used alone or in combination of two or more.
[0203] The type of polar group possessed by component (III) and component (IV) is not particularly limited, and examples thereof include:
[0204] Epoxy and carboxyl, carbonyl, ester, imidazole, hydroxyl, amino, thiol, benzoxazine, carbodiimide, phenolic hydroxyl;
[0205] Amino group and carboxyl group, carbonyl group, hydroxyl group, anhydride group, sulfonic acid group, aldehyde group;
[0206] Isocyanate group and hydroxyl group, carboxylic acid group, phenolic hydroxyl group;
[0207] Anhydride group and hydroxyl group;
[0208] Silanol group and hydroxyl group, carboxylic acid group;
[0209] Halogen and carboxylic acid group, carboxylate group, amino group, phenol group, and mercapto group;
[0210] Alkoxy and hydroxyl, alkoxide, and amino groups;
[0211] Maleimide group and cyanate group; and so on.
[0212] Whether these polar groups are bonded to component (III) or component (IV) can be arbitrarily selected.
[0213] Furthermore, even when the polar group of component (III) and the polar group of component (IV) do not react directly, the case where the reaction can proceed by adding a curing accelerator such as a catalyst is also included in the definition of showing "reactivity".
[0214] For example, when component (III) is a polar resin having an epoxy group and component (IV) is a curing agent having an acid anhydride group, the reactivity between the epoxy group and the acid anhydride group is generally very low, but by adding a compound having an amino group as a curing accelerator, the epoxy group of component (III) reacts with the amino group, and a part or all of the epoxy group of component (III) is converted into a hydroxyl group. The hydroxyl group reacts with the acid anhydride group of the curing agent of component (IV), and the resin composition is cured.
[0215] From the perspective of reactivity, the molar ratio of the polar resin of component (III) to the curing agent of component (IV) is preferably polar group of component (III): polar group of component (IV) = 1:0.01 to 1:20, more preferably 1:0.05 to 1:15, and even more preferably 1:0.1 to 1:10, in terms of the molar ratio of the polar groups.
[0216] Regarding component (IV): a curing agent, examples of a curing agent having an ester group include EXB9451, EXB9460, EXB, 9460S, HPC8000-65T, HPC8000H-65TM, EXB8000L-65TM, EXB8150-65T, EXB9416-70BK manufactured by DIC Corporation, and YLH1026, DC808, YLH1026, YLH1030, and YLH1048 manufactured by Mitsubishi Chemical Corporation.
[0217] Examples of curing agents having a hydroxyl group include MEH-7700, MEH-7810, MEH-7851, NHN, CBN, and GPH manufactured by Nippon Kayaku Co., Ltd., SN170, SN170, SN180, SN190, SN475, SN485, SN495, SN-495V, and SN375 manufactured by Nippon Steel & Sumitomo Chemical Co., Ltd., TD-2090, LA-7052, LA-7054, LA-1356, LA-3018-50P, and EXB-9500 manufactured by DIC Corporation, and the like.
[0218] Examples of the curing agent having a benzoxazine group include ODA-BOZ manufactured by JFE Chemical Co., Ltd., HFB2006M manufactured by Showa High Molecular Co., Ltd., and Pd and Fa manufactured by Shikoku Chemical Industry Co., Ltd.
[0219] Examples of the curing agent having an isocyanate group include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylidene))benzene, bis(4-cyanatephenyl)sulfide, and bis(4-cyanatephenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; prepolymers obtained by partially triazinizing these cyanate resins; and the like. Examples of commercially available products include PT30, PT60, ULL-950S, BA230, and BA230S75 manufactured by Lonza Japan.
[0220] Examples of the curing agent having a carbodiimide group include V-03 and V-07 manufactured by Nisshinbo Chemical Co., Ltd.
[0221] Examples of the curing agent having an amino group include 4,4'-methylenebis(2,6-dimethylaniline), diphenyldiaminosulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, metaphenylenediamine, metaphenylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino- 4-hydroxyphenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. Commercially available products include KAYABOND C-200S, KAYABOND C-100, KAYAHARD AA, KAYAHARD AB, KAYAHARD AS manufactured by Nippon Kayaku Co., Ltd., and Epicure W manufactured by Mitsubishi Chemical Corporation.
[0222] In addition, from the viewpoint of reactivity, the amino group is preferably a primary amine and / or a secondary amine, and more preferably a primary amine.
[0223] Examples of the curing agent having an acid anhydride group include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyrophthalic anhydride, and the like. Tetracarboxylic dianhydride, benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic anhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphthol[1,2-C]furan-1,3-dione, ethylene glycol bis(trimellitic anhydride), styrene-maleic acid resin obtained by copolymerization of styrene and maleic acid, and the like polymer type acid anhydrides, etc.
[0224] In addition, the compound having at least two structures having free radical reactivity also has the function of reacting with the component (III) to cure the resin composition. The compound can also be used as a curing agent for the component (IV).
[0225] Examples of the compound having at least two structures having free radical reactivity include allyl monomers such as triallyl isocyanurate (Taic manufactured by Mitsubishi Chemical Corporation), tris(2-hydroxyethyl)isocyanurate, diallyl fumarate, diallyl adipate, triallyl citrate, and diallyl hexahydrophthalate.
[0226] When the resin composition of the present embodiment contains component (III), the polar resin as component (III) is preferably at least one selected from the group consisting of epoxy resins, polyimide resins, polyphenylene ether resins, liquid crystal polyester resins, and fluorine resins from the aspect of heat resistance. More preferably, it is at least one selected from the group consisting of epoxy resins, polyimide resins, and polyphenylene ether resins.
[0227] In addition, from the perspective of adhesion to metal foil such as copper foil, it is particularly preferred that as component (III), the polar resin is at least one selected from the group consisting of epoxy resins, polyimide resins, and polyphenylene ether resins, and as component (I), a hydrogenated conjugated diene copolymer having a vinyl aromatic monomer unit content of 35 to 75% by mass is used.
[0228] As polyimide resin, as long as there is an imide bond in the repeating unit, it belongs to the category of polyimide resin. For example, a common polyimide structure obtained by polycondensation (imide bonding) of tetracarboxylic acid or its dianhydride with diamine can be cited. From the aspect of curability, it is preferred to have an unsaturated group at the end of the above-mentioned polyimide structure. As a polyimide resin having an unsaturated group at the end, for example, maleimide type polyimide resin, nadic imide type polyimide resin, allyl nadic imide type polyimide resin, etc. can be cited.
[0229] Examples of the tetracarboxylic acid or its dianhydride include, but are not limited to, aromatic tetracarboxylic dianhydride, alicyclic tetracarboxylic dianhydride, aliphatic tetracarboxylic dianhydride, etc. These may be used alone or in combination of two or more.
[0230] The diamine is not particularly limited, and examples thereof include aromatic diamines, alicyclic diamines, aliphatic diamines, etc., which are generally used in the synthesis of polyimide. These may be used alone or in combination of two or more.
[0231] In addition, from the perspective of low dielectric constant and low dielectric loss tangent of the resin composition and cured product of this embodiment, at least one of the above-mentioned tetracarboxylic acid or its dianhydride or diamine may have one or more functional groups selected from the group consisting of fluorine, trifluoromethyl, hydroxyl, sulfonic, carbonyl, heterocyclic, long-chain alkyl, and allyl.
[0232] In addition, as the polyimide resin, a commercially available polyimide resin can be used. Examples include, but are not limited to, Neoprim (registered trademark) C-3650 (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name), Neoprim C-3G30 (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name), Neoprim C-3450 (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name), Neoprim P500 (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name), BT (bismaleimide-triazine) resin (manufactured by Mitsubishi Gas Chemical Co., Ltd.), JL-20 (manufactured by Shin Nippon Rika Co., Ltd., trade name) (the varnish of these polyimide resins may contain silicon oxide), Rikacoat SN20 manufactured by Shin Nippon Rika Co., Ltd., and Rikacoat SN20 manufactured by Shin Nippon Rika Co., Ltd. PN20, Pyre-ML manufactured by IST, Upia-AT, Upia-ST, Upia-NF, Upia-LB manufactured by Ube Industries, PIX-1400, PIX-3400, PI2525, PI2610, HD-3000, AS-2600 manufactured by Hitachi Chemical, HPC-5000, HPC-5012, HPC-1000, HPC-5020, HPC-3010, HPC-6000, HPC-9000, HCI-7000, HCI-1000S, HCI-1200E, HCI-1300 manufactured by Showa Denko K.K., BMI-2300 manufactured by Yamato Kasei Kogyo Co., Ltd., and MIR-3000 manufactured by Shin Nippon Kayaku Co., Ltd.
[0233] The polyphenylene ether-based resin as component (III) may be any resin that falls within the category of polyphenylene ether resins and contains a phenylene ether unit as a repeating structural unit and may contain other structural units in addition to the phenylene ether unit.
[0234] As a homopolymer having a phenylene ether unit, there is no particular limitation on whether the phenylene in the phenylene unit has a substituent. Examples of the substituent include ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl and other acryloyl groups, cyclohexyl and other cyclic alkyl groups, vinyl, allyl, isopropenyl, 1-butenyl, 1-pentenyl, p-vinylphenyl, p-isopropenylphenyl, m-vinylphenyl, m-isopropenylphenyl, o-vinylphenyl, o-isopropenylphenyl, p-vinylbenzyl, p-isopropenylbenzyl, m-vinylbenzyl, m-isopropenylbenzyl, o-vinylbenzyl, o-isopropenylbenzyl, p-vinylphenylvinyl, p-vinylphenylpropenyl, p-vinylphenylbutenyl, m-vinylphenylvinyl, m-vinylphenylpropenyl, m-vinylphenylbutenyl, o-vinylphenylvinyl Substituents containing unsaturated bonds such as hydroxyl, carboxyl, carbonyl, thiocarbonyl, acyl halide, anhydride, carboxylic acid, thiocarboxylic acid, aldehyde, thialdehyde, carboxylate, amide, sulfonic acid, sulfonate, phosphoric acid, phosphate, amino, imino, nitrile, pyridine, quinoline, epoxy, thioepoxy, thioether, isocyanate, isothiocyanate, halogenated silicon, silanol, alkoxysilyl, halogenated tin, boric acid, boron-containing, borate, alkoxytin and phenyltin. From the aspect of the curability of the resin composition of the present embodiment, the polyphenylene ether resin preferably has a polar group (the polar group has free radical reactivity and / or reactivity with the component (IV) curing agent).
[0235] From the perspective of curability of the resin composition of this embodiment, the molecular weight of the polyphenylene ether resin as component (III) is preferably 100,000 or less, more preferably 50,000 or less, and even more preferably 10,000 or less. The polyphenylene ether resin may be linear, cross-linked, or branched.
[0236] The liquid crystal polyester resin as the component (III) may be any polyester that forms an anisotropic melt phase, as long as it falls within the category of liquid crystal polyester resins.
[0237] For example, "X7G" manufactured by Eastman Kodak Co., Ltd., Xyday manufactured by Dartco, Inc., EKONOL manufactured by Sumitomo Chemical Co., Ltd., Vectra manufactured by Celanese Corporation, and the like can be cited.
[0238] The fluorine-based resin as the component (III) may be any resin that falls within the category of fluorine-based resins and is an olefin-based polymer containing a fluorine group.
[0239] Examples of the fluorine-based resin include polytetrafluoroethylene, perfluoroalkoxyalkane, ethylene-tetrafluoroethylene copolymer, perfluoroethylene-propylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, and ethylene-chlorotrifluoroethylene copolymer.
[0240] The epoxy resin as component (III) may be any resin that falls within the category of epoxy resins, and preferably has two or more epoxy groups in one molecule from the viewpoint of strength.
[0241] The epoxy resin may be used alone or in combination of two or more.
[0242] Examples of the epoxy resin include bixylenol-type epoxy resins, bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, bisphenol S-type epoxy resins, bisphenol AF-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, naphthol novolac-type epoxy resins, phenol novolac-type epoxy resins, tert-butyl-catechol-type epoxy resins, naphthalene-type epoxy resins, naphthol-type epoxy resins, anthracene-type epoxy resins, glycidylamine-type epoxy resins, glycidylester-type epoxy resins, cresol novolac-type epoxy resins, biphenyl-type epoxy resins, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane-type epoxy resins, cyclohexanedimethanol-type epoxy resins, naphthylene ether-type epoxy resins, trimethylol-type epoxy resins, and tetraphenylethane-type epoxy resins.
[0243] In addition, from the aspect of reactivity with component (I): hydrogenated conjugated diene copolymer, when epoxy resin is used as component (III), component (IV) curing agent is preferably contained together. In this case, polar groups possessed by component (IV) curing agent include, for example, carboxyl, imidazole, hydroxyl, amino, thiol, benzoxazine, and carbodiimide. From the aspect of reactivity, carboxyl, imidazole, hydroxyl, benzoxazine, and carbodiimide are preferred. From the aspect of dielectric properties, hydroxyl, carboxyl, imidazole, benzoxazine, and carbodiimide are more preferred, and hydroxyl, carboxyl, and carbodiimide are further preferred.
[0244] In addition, when two or more polar resins with different free radical reactivity are used as component (III), from the aspect of the curability of the resin composition of this embodiment, it is preferred to use component (II): a free radical initiator and component (IV): a curing agent together. For example, when a maleimide-type polyimide resin with excellent free radical reactivity and a bisphenol A epoxy resin without free radical reactivity are used as component (III), from the aspect of curability, it is preferred to add the above-mentioned component (II): a free radical initiator and the above-mentioned component (IV): a curing agent.
[0245] In addition, when a polar resin with a high melting point and high rigidity is used as component (III): polar resin, the resin composition of this embodiment may not include component (IV). As the polar resin with a high melting point and high rigidity belonging to component (III), for example, fluorine-based resins such as liquid crystal polyester resins and polytetrafluoroethylene can be cited.
[0246] When the component (III) has a high melting point and high rigidity, the strength required for practical use tends to be obtained even when the component (IV) is not contained.
[0247] (Ingredient (V): additive)
[0248] The resin composition of the present embodiment may further contain various additives such as a curing accelerator, a filler, and a flame retardant as a component (V).
[0249] The components contained as additives for the hydrogenated conjugated diene copolymer as component (I) are also the same as the components (V) of the above-mentioned resin composition.
[0250] The curing accelerator is added for the purpose of promoting the reactivity between the above-mentioned components, and any known curing accelerator may be used, for example, phosphorus curing accelerators, amine curing accelerators, imidazole curing accelerators, guanidine curing accelerators, metal curing accelerators, etc. may be mentioned.
[0251] The curing accelerator may be used alone or in combination of two or more.
[0252] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.
[0253] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, and 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene are preferred.
[0254] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino- Imidazole compounds such as 6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and adducts of imidazole compounds with epoxy resins, preferably 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole.
[0255] As the imidazole-based curing accelerator, a commercially available product may be used, and examples thereof include P200-H50 manufactured by Mitsubishi Chemical Corporation.
[0256] Examples of the guanidine-based curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine. Preferred examples include dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene.
[0257] Examples of the metal curing accelerator include organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin.
[0258] Examples of the organic metal complex include, but are not limited to, organic cobalt complexes such as cobalt (II) acetylacetonate and cobalt (III) acetylacetonate, organic copper complexes such as copper (II) acetylacetonate, organic zinc complexes such as zinc (II) acetylacetonate, organic iron complexes such as iron (III) acetylacetonate, organic nickel complexes such as nickel (II) acetylacetonate, and organic manganese complexes such as manganese (II) acetylacetonate.
[0259] Examples of the organic metal salt include, but are not limited to, zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, and the like.
[0260] As fillers, there can be mentioned, but are not limited to, inorganic fillers such as silicon oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, calcium sulfate, barium sulfate, carbon black, glass fiber, glass beads, glass hollow spheres, glass flakes, graphite, titanium oxide, potassium titanate whiskers, carbon fiber, aluminum oxide, kaolin, silicic acid, calcium silicate, quartz, mica, talc, clay, zirconium oxide, potassium titanate, aluminum oxide, and metal particles; and organic fillers such as wood chips, wood powder, pulp, and cellulose nanofibers.
[0261] These fillers may be used alone or in combination of plural types.
[0262] The shapes of these fillers are not particularly limited and may be any shapes such as flaky, spherical, granular, powdery, or amorphous.
[0263] The resin composition or cured product of the present embodiment is often exposed to high temperature during molding, and in order to prevent shrinkage due to temperature changes and deformation of the molded body, the filler preferably has a small linear expansion coefficient. From the aspect of reducing the linear expansion coefficient, silicon oxide is preferably used as the filler, and examples of silicon oxide include amorphous silicon oxide, fused silicon oxide, crystalline silicon oxide, synthetic silicon oxide, hollow silicon oxide, and the like.
[0264] Examples of the flame retardant include halogen flame retardants such as bromine compounds, phosphorus flame retardants such as aromatic compounds, metal hydroxides, alkyl sulfonates, antimony trioxide, aluminum hydroxide, magnesium hydroxide, zinc borate, and flame retardants containing aromatic bromine compounds such as hexabromobenzene, decabromodiphenylethane, 4,4-dibromobiphenyl, and ethylenebistetrabromophthalimide.
[0265] These flame retardants may be used alone or in combination of two or more.
[0266] The flame retardants mentioned above also include so-called flame retardant auxiliary agents which have low flame retardancy-expressing effects by themselves but can synergistically exert more excellent effects by being used in combination with other flame retardants.
[0267] The filler and the flame retardant may be those which have been surface-treated in advance with a surface treatment agent such as a silane coupling agent.
[0268] Examples of the surface treatment agent include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. These substances may be used alone or in combination of a plurality of them.
[0269] There are no particular limitations on other additives as long as they are additives commonly used in mixing resin compositions and cured products.
[0270] Other additives include, but are not limited to, pigments and / or colorants such as carbon black and titanium oxide; lubricants such as stearic acid, behenic acid, zinc stearate, calcium stearate, magnesium stearate, and ethylene bisstearamide; anti-sticking agents; plasticizers such as organic polysiloxanes, phthalates, adipic acid ester compounds, azelaic acid ester compounds, and mineral oils; antioxidants such as hindered phenol and phosphorus heat stabilizers; hindered amine light stabilizers; benzotriazole ultraviolet absorbers; antistatic agents; organic fillers; thickeners; defoamers; leveling agents; resin additives such as adhesion-imparting agents; other additives or mixtures thereof.
[0271] From the viewpoint of the aforementioned low dielectric constant and low dielectric loss tangent, the resin composition of the present embodiment preferably does not contain a pigment, a colorant, a lubricant, a release agent, or an antistatic agent.
[0272] The resin composition in the present embodiment may be obtained by melt-kneading the components, or by dissolving and stirring the components in a solvent capable of dissolving the components (hereinafter referred to as "varnish"). From the viewpoint of handling properties, varnish is preferred.
[0273] Examples of the solvent constituting the varnish include ketones such as acetone, methyl ethyl ketone (MEK), cyclohexanone, and γ-butyrolactone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, carbitol acetate, and diethylene glycol monoethyl ether monoacetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; amide solvents such as dimethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone, etc. The organic solvent may be used alone or in combination of two or more.
[0274] [cured material]
[0275] The cured product of the present embodiment includes the hydrogenated conjugated diene-based copolymer of the present embodiment described above.
[0276] In addition, the cured product of the present embodiment is a cured product of the resin composition of the present embodiment, obtained by subjecting the above-mentioned resin composition to a curing reaction at an arbitrary temperature and time. Its concept includes not only a completely cured product but also a method (semi-cured) in which only a portion of the resin composition is cured and contains uncured components.
[0277] In the process of producing the laminate described later, a step of further curing the cured product may be performed.
[0278] The reaction temperature of the curing process of the cured product of the present embodiment is preferably 80°C or more, more preferably 100°C or more, and further preferably 120°C or more. As the reaction time, it is preferably 10 to 240 minutes, more preferably 20 to 230 minutes, and further preferably 30 to 220 minutes. In the case where the resin composition of the present embodiment is a varnish, it is preferably subjected to a curing reaction after drying to remove the solvent. As a drying method, it can be implemented by existing known methods such as heating and hot air blowing, preferably at a low temperature lower than the curing reaction temperature. The amount of solvent in the dried resin composition is preferably 10% by mass or less, more preferably 5% by mass or less.
[0279] [Resin film]
[0280] The resin film of this embodiment contains the resin composition of this embodiment.
[0281] The resin film of the present embodiment is obtained, for example, by spreading a varnish composed of the resin composition of the present embodiment described above on a predetermined support in a uniform thin film form, and drying the varnish to remove the solvent. The resin film can be stored in a roll form.
[0282] [Prepreg]
[0283] The prepreg of the present embodiment includes a base material and the resin composition of the present embodiment impregnated, coated or laminated on the base material. That is, the prepreg of the present embodiment is a composite of the resin composition of the present embodiment and the base material.
[0284] The prepreg is obtained by, for example, impregnating a base material such as glass cloth with a varnish which is the resin composition of the present embodiment described above, and then removing the solvent by the above-mentioned drying method.
[0285] As the substrate, for example, there can be cited various glass cloths such as coarse yarn cloth, cloth, chopped strand mat, surface mat, etc.; asbestos cloth, metal fiber cloth, and other synthetic or natural inorganic fiber cloths; woven fabrics or non-woven fabrics obtained from liquid crystal fibers such as wholly aromatic polyamide fibers, wholly aromatic polyester fibers, polybenzoxazole fibers, etc.; natural fiber cloths such as cotton cloth, linen, and felt; natural cellulose-based substrates such as carbon fiber cloth, kraft paper, cotton paper, and cloth obtained from paper-glass mixed fibers; polytetrafluoroethylene porous membranes, etc. From the perspective of dielectric properties, glass cloth is preferred.
[0286] These substrates can be used alone or in combination of two or more.
[0287] The ratio of the solid content of the resin composition of the present embodiment in the prepreg is preferably 30 to 80% by mass, more preferably 40 to 70% by mass. By making the above ratio more than 30% by mass, there is a tendency that insulation reliability is more excellent when the prepreg is used for electronic substrate applications, etc. By making the above ratio less than 80% by mass, there is a tendency that mechanical properties such as rigidity are more excellent in applications such as electronic substrates.
[0288] [laminated body]
[0289] The laminate of the present embodiment includes the above-mentioned resin film and metal foil. Alternatively, the laminate of the present embodiment may include a cured product of the above-mentioned prepreg and metal foil.
[0290] The laminate of the present embodiment can be manufactured, for example, by the following steps: step (a), laminating a resin film composed of the resin composition of the present embodiment on a substrate to form a resin layer; step (b), heating and pressurizing the above-mentioned resin layer to flatten it and solidify the resin layer; and step (c), further forming a specified wiring layer composed of metal foil on the above-mentioned resin layer; and so on.
[0291] In step (a), the method for laminating the resin film on the substrate is not particularly limited. For example, there can be mentioned a method of laminating using a multi-stage press, a vacuum press, a normal pressure laminator, a laminator that performs heating and pressurizing under vacuum, etc., and preferably, a method using a laminator that performs heating and pressurizing under vacuum is used.
[0292] In this method using a laminator, even if the target electronic circuit board has fine wiring circuits on the surface, the spaces between the circuits can be filled with resin without voids. In addition, lamination may be performed in batches or continuously using a roller or the like.
[0293] As the substrate, in addition to the substrate constituting the prepreg, for example, glass epoxy substrates, metal substrates, polyester substrates, polyimide substrates, polyphenylene ether substrates, fluororesin substrates, etc. can be cited. The surface of the laminated resin layer of the substrate can be roughened in advance, and the number of substrate layers is not limited.
[0294] In the above step (b), the resin film and the substrate laminated in the above step (a) are pressed under heating to be flattened. The conditions can be arbitrarily adjusted according to the type of substrate and the composition of the resin film, for example, the temperature is preferably in the range of 100 to 300°C, the pressure is 0.2 to 20 MPa, and the time is 30 to 180 minutes.
[0295] In the above step (c), the resin film and the substrate are pressed under heating to further form a predetermined wiring layer composed of a metal foil on the produced resin layer. The formation method is not particularly limited, and existing well-known methods can be cited, for example, etching methods such as subtractive methods, semi-additive methods, etc. can be cited.
[0296] The subtractive method is a method in which a resist layer having a shape corresponding to a desired pattern shape is formed on a metal layer, and the metal layer in a portion where the resist has been removed is dissolved away with a reagent by subsequent development treatment, thereby forming a desired wiring.
[0297] The semi-additive method is a method in which a metal coating is formed on the surface of a resin layer by electroless plating, a plating resist layer having a shape corresponding to a desired pattern is formed on the metal coating, a metal layer is then formed by electrolytic plating, and then the unnecessary electroless plating layer is removed using a reagent or the like to form a desired wiring layer.
[0298] In addition, holes such as vias can be formed in the resin layer as needed, and the method for forming the holes is not particularly limited, and existing known methods can be used. As the method for forming the holes, for example, NC drills, carbon dioxide lasers, UV lasers, YAG lasers, plasma, etc. can be used.
[0299] [Metal-clad laminate]
[0300] The laminate of the present embodiment described above may be in a plate shape or may be a flexible laminate having flexibility.
[0301] The laminated body of the present embodiment may be a metal-clad laminate.
[0302] The metal-clad laminate is obtained by laminating and curing the resin composition of the present embodiment or the prepreg of the present embodiment and a metal foil, and a part of the metal foil is removed from the metal-clad laminate.
[0303] The metal-clad laminate preferably has a form in which a cured product of a prepreg (also referred to as a "cured product composite") and a metal foil are laminated and closely adhered to each other, and can be suitably used as a material for an electronic circuit board.
[0304] Examples of the metal foil include aluminum foil and copper foil. Among these, copper foil is preferred because of its low electrical resistance.
[0305] The cured product of the prepreg combined with the metal foil may be a single sheet or a plurality of sheets, and the cured product may be processed into a metal-clad laminate by laminating the metal foil on one or both sides of the cured product according to the application.
[0306] As a method for manufacturing the above-mentioned metal-clad laminate, for example, the following method can be cited: forming a prepreg composed of the resin composition of this embodiment and a substrate, stacking it with a metal foil, and then curing the resin composition to obtain a metal-clad laminate in which a cured prepreg and a metal foil are stacked.
[0307] One of the particularly preferred uses of the metal-clad laminate is a printed wiring board. In the printed wiring board, it is preferred that at least a portion of the metal foil is removed from the metal-clad laminate. That is, in this case, the metal-clad laminate becomes an intermediate product of the printed wiring board.
[0308] The above-mentioned printed wiring board can be made by the method of pressurized heating molding using the prepreg of the above-mentioned present embodiment. As a substrate, the same substrate as the substrate of the above-mentioned prepreg can be used. The above-mentioned printed wiring board has excellent strength and electrical properties (low dielectric constant and low dielectric loss tangent) by comprising the resin combination of the present embodiment, and then can suppress the change of electrical properties accompanied by environmental changes, and has excellent insulation reliability and mechanical properties.
[0309] [Materials for electronic circuit boards, printed wiring boards]
[0310] The material for an electronic circuit board of the present embodiment includes a cured product of the resin composition of the present embodiment.
[0311] The material for the electronic circuit board of the present embodiment can be produced using the resin composition and / or varnish of the present embodiment described above.
[0312] The material for the electronic circuit substrate of the present embodiment comprises at least one selected from the group consisting of a cured product of the above-mentioned resin composition, a resin film comprising the resin composition of the present embodiment or its cured product, and a prepreg as a composite of a substrate and the resin composition. The material for the electronic circuit substrate of the present embodiment can be used as a printed wiring board having a metal foil with a resin, for example.
[0313] Example
[0314] The present embodiment will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples and comparative examples.
[0315] The methods for structural identification and physical property measurement of the hydrogenated conjugated diene copolymer or unhydrogenated conjugated diene copolymer (component (I)) (hereinafter sometimes referred to as conjugated diene copolymer) in the following Examples and Comparative Examples are as follows.
[0316] [Methods for structural identification and physical property measurement of conjugated diene copolymers]
[0317] ((1) Content of vinyl aromatic monomer units in conjugated diene copolymer)
[0318] Using the conjugated diene copolymer before hydrogenation, the content of the vinyl aromatic monomer unit in the copolymer was measured using an ultraviolet spectrophotometer (UV-2450 manufactured by Shimadzu Corporation).
[0319] ((2) Vinyl Bond Amount of Conjugated Diene Copolymer)
[0320] The conjugated diene copolymer before hydrogenation was used to measure the vinyl bond content using an infrared spectrophotometer (FT / IR-230, manufactured by JASCO Corporation).
[0321] The vinyl bond content of the copolymer was calculated by the Hampton method.
[0322] ((3) Molecular Weight and Molecular Weight Distribution of Conjugated Diene Copolymer)
[0323] The molecular weight of the conjugated diene copolymer of the component (I) before modification and hydrogenation was measured by GPC [apparatus: LC-10 (manufactured by Shimadzu Corporation), column: TSKgel GMHXL (4.6 mm×30 cm)].
[0324] Tetrahydrofuran was used as the solvent.
[0325] Regarding the measurement conditions, the measurement was performed at a temperature of 35°C.
[0326] The molecular weight is a weight average molecular weight obtained by determining the peak molecular weight of the chromatogram using a calibration curve determined by measurement of commercially available standard polystyrene (created using the peak molecular weight of standard polystyrene).
[0327] It should be noted that, regarding the molecular weight in the case of having a plurality of peaks in the chromatogram, it is set to the average molecular weight obtained based on the molecular weight of each peak and the composition ratio of each peak (obtained from the area ratio of each peak in the chromatogram). In addition, the molecular weight distribution is the ratio (Mw / Mn) of the obtained weight average molecular weight (Mw) to the number average molecular weight (Mn).
[0328] ((4) Hydrogenation rate of double bonds of conjugated diene monomer units in conjugated diene copolymer)
[0329] Using the hydrogenated component (I): hydrogenated conjugated diene copolymer, the hydrogenation rate of the double bonds of the conjugated diene monomer units was measured using a nuclear magnetic resonance apparatus (DPX-400 manufactured by BRUKER).
[0330] [Hydrogenated or non-hydrogenated conjugated diene copolymer (sometimes referred to as conjugated diene copolymer), materials for resin composition]
[0331] (Preparation of Hydrogenation Catalyst)
[0332] The hydrogenation catalyst used when producing the hydrogenated conjugated diene copolymer in the Production Examples and Comparative Production Examples described below was prepared by the following method.
[0333] A reaction container equipped with a stirring device was purged with nitrogen, and 1 liter of dried and purified cyclohexane was added thereto.
[0334] Next, 100 mmol of bis(η5-cyclopentadienyl)titanium dichloride was added, and a n-hexane solution containing 200 mmol of trimethylaluminum was added while the mixture was fully stirred, and the mixture was reacted at room temperature for about 3 days. Thus, a hydrogenation catalyst was obtained.
[0335] (Component (I): conjugated diene copolymer)
[0336] The conjugated diene-based copolymer of a vinyl aromatic compound and a conjugated diene compound is prepared as follows.
[0337] Tables 1 to 3 show the structures and physical property values of the conjugated diene copolymers.
[0338] <(Production Example 1) Hydrogenated conjugated diene copolymer (1)>
[0339] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.
[0340] First, a cyclohexane solution (concentration: 20% by mass) containing 10 parts by mass of styrene and 90 parts by mass of butadiene was added.
[0341] Next, 2.14 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.35 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 20 minutes.
[0342] Methanol was then added to terminate the polymerization reaction, thereby obtaining a conjugated diene copolymer.
[0343] The conjugated diene copolymer obtained as above had a styrene content of 10% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, and the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 55%.
[0344] The obtained conjugated diene copolymer was further treated with 90 ppm of the above prepared hydrogenation catalyst based on Ti per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 0.5 hours to obtain a hydrogenated conjugated diene copolymer (1).
[0345] The hydrogenation rate of the obtained hydrogenated conjugated diene copolymer (1) was 50%.
[0346] <(Production Example 2): Hydrogenated conjugated diene copolymer (2)>
[0347] The same operation as in the hydrogenated conjugated diene copolymer (1) was carried out except that 20 parts by mass of styrene and 80 parts by mass of butadiene were added.
[0348] The hydrogenated conjugated diene copolymer (2) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 55%, and the hydrogenation rate was 51%.
[0349] <(Production Example 3): Hydrogenated conjugated diene copolymer (3)>
[0350] The same operation as in the hydrogenated conjugated diene copolymer (1) was carried out except that 40 parts by mass of styrene and 60 parts by mass of butadiene were added, 1.8 parts by mass of n-butyl lithium was added based on 100 parts by mass of all monomers, and 0.18 mol of TMEDA was added based on 1 mol of n-butyl lithium.
[0351] The hydrogenated conjugated diene copolymer (3) obtained as described above had a styrene content of 40% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond amount: unit (a) / butadiene) was 54%, and the hydrogenation rate was 49%.
[0352] <(Production Example 4): Hydrogenated conjugated diene copolymer (4)>
[0353] The same operation as in the hydrogenated conjugated diene copolymer (1) was carried out except that 60 parts by mass of styrene and 40 parts by mass of butadiene were added, 1.56 parts by mass of n-butyl lithium was added based on 100 parts by mass of all monomers, and 0.19 mol of TMEDA was added based on 1 mol of n-butyl lithium.
[0354] The hydrogenated conjugated diene copolymer (4) obtained as described above had a styrene content of 60% by mass and a weight average molecular weight of 0.5×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 55%, and the hydrogenation rate was 50%.
[0355] <(Production Example 5): Hydrogenated conjugated diene copolymer (5)>
[0356] The same operation as in the hydrogenated conjugated diene copolymer (1) was carried out except that 85 parts by mass of styrene and 15 parts by mass of butadiene were added, 1.28 parts by mass of n-butyl lithium was added based on 100 parts by mass of all monomers, and 0.24 mol of TMEDA was added based on 1 mol of n-butyl lithium.
[0357] The hydrogenated conjugated diene copolymer (5) obtained as described above had a styrene content of 85% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond amount: unit (a) / butadiene) was 56%, and the hydrogenation rate was 52%.
[0358] <(Production Example 6) Hydrogenated conjugated diene copolymer (6)>
[0359] The same operation as in the hydrogenated conjugated diene copolymer (2) was carried out except that 0.67 parts by mass of n-butyl lithium was added to 100 parts by mass of all monomers and 0.33 mol of TMEDA was added to 1 mol of n-butyl lithium.
[0360] The hydrogenated conjugated diene copolymer (6) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 1.5×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 54%, and the hydrogenation rate was 50%.
[0361] <(Production Example 7): Hydrogenated conjugated diene copolymer (7)>
[0362] The same operation as in the hydrogenated conjugated diene copolymer (2) was carried out except that 0.51 parts by mass of n-butyl lithium was added based on 100 parts by mass of all monomers and 0.37 mol of TMEDA was added based on 1 mol of n-butyl lithium.
[0363] The hydrogenated conjugated diene copolymer (7) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 2.0×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 55%, and the hydrogenation rate was 50%.
[0364] <(Production Example 8): Hydrogenated conjugated diene copolymer (8)>
[0365] The same operation as in the hydrogenated conjugated diene copolymer (2) was carried out except that 0.34 parts by mass of n-butyl lithium was added based on 100 parts by mass of all monomers and 0.44 mol of TMEDA was added based on 1 mol of n-butyl lithium.
[0366] The hydrogenated conjugated diene copolymer (8) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 3.0×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 55%, and the hydrogenation rate was 50%.
[0367] <(Production Example 9): Hydrogenated conjugated diene copolymer (9)>
[0368] The same operation as in the hydrogenation of the conjugated diene copolymer (2) was carried out except that the hydrogenation reaction time was changed to 0.15 hours.
[0369] The hydrogenated conjugated diene copolymer (9) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 55%, and the hydrogenation rate was 11%.
[0370] <(Production Example 10): Hydrogenated conjugated diene copolymer (10)>
[0371] The same operation as in the hydrogenation of the conjugated diene copolymer (2) was carried out except that the hydrogenation reaction time was changed to 0.25 hours.
[0372] The hydrogenated conjugated diene copolymer (10) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×104 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 55%, and the hydrogenation rate was 35%.
[0373] <(Production Example 11): Hydrogenated conjugated diene copolymer (11)>
[0374] The same operation as in the hydrogenation of the conjugated diene copolymer (2) was carried out except that the hydrogenation reaction time was changed to 0.75 hours.
[0375] The hydrogenated conjugated diene copolymer (11) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 55%, and the hydrogenation rate was 85%.
[0376] <(Production Example 12): Hydrogenated conjugated diene copolymer (12)>
[0377] The same operation as in the hydrogenation of the conjugated diene copolymer (2) was carried out except that the hydrogenation reaction time was changed to 1.00 hour.
[0378] The hydrogenated conjugated diene copolymer (12) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 55%, and the hydrogenation rate was 100%.
[0379] <(Production Example 13): Hydrogenated conjugated diene copolymer (13)>
[0380] The same operation as in the hydrogenation of the conjugated diene copolymer (2) was carried out except that the amount of TMEDA was 0.43 mol relative to 1 mol of n-butyllithium and the hydrogenation reaction time was 0.25 hours.
[0381] The hydrogenated conjugated diene copolymer (13) obtained as above had a styrene content of 40% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond amount: unit (a) / butadiene) was 76%, and the hydrogenation rate was 35%.
[0382] <(Production Example 14): Hydrogenated conjugated diene copolymer (14)>
[0383] The same operation as in the hydrogenation of the conjugated diene copolymer (2) was carried out except that the amount of TMEDA was 0.06 mol relative to 1 mol of n-butyllithium and the hydrogenation reaction time was 0.25 hours.
[0384] The hydrogenated conjugated diene copolymer (14) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 21%, and the hydrogenation rate was 36%.
[0385] <(Production Example 15) Hydrogenated conjugated diene copolymer (15)>
[0386] The same operation as in the hydrogenation of the conjugated diene copolymer (2) was carried out except that the amount of TMEDA was 0.41 mol relative to 1 mol of n-butyllithium and the hydrogenation reaction time was 0.25 hours.
[0387] The hydrogenated conjugated diene copolymer (15) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 75%, and the hydrogenation rate was 35%.
[0388] <(Production Example 16): Hydrogenated conjugated diene copolymer (16)>
[0389] The same operation as in the hydrogenation of the conjugated diene copolymer (2) was carried out except that 0.41 mol of TMEDA was added to 1 mol of n-butyllithium.
[0390] The hydrogenated conjugated diene copolymer (16) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 75%, and the hydrogenation rate was 50%.
[0391] <(Production Example 17): Hydrogenated conjugated diene copolymer (17)>
[0392] The same operation as in the hydrogenation of the conjugated diene copolymer (16) was carried out except that the hydrogenation reaction time was changed to 0.75 hours.
[0393] The hydrogenated conjugated diene copolymer (17) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4, the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 75%, and the hydrogenation rate was 86%.
[0394] <(Production Example 18): Hydrogenated conjugated diene copolymer (18)>
[0395] The same operation as in the hydrogenated conjugated diene copolymer (2) was carried out except that 0.45 mol of TMEDA was added to 1 mol of n-butyllithium and the polymerization temperature was set at 60°C.
[0396] The hydrogenated conjugated diene copolymer (18) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 84%, and the hydrogenation rate was 51%.
[0397] <(Production Example 19): Hydrogenated conjugated diene copolymer (19)>
[0398] The same operation as in the hydrogenated conjugated diene copolymer (2) was carried out except that 0.99 parts by mass of n-butyl lithium was added to 100 parts by mass of all monomers and 0.45 mol of TMEDA was added to 1 mol of n-butyl lithium.
[0399] The hydrogenated conjugated diene copolymer (19) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 1.0×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 74%, and the hydrogenation rate was 50%.
[0400] <(Production Example 20): Hydrogenated conjugated diene copolymer (20)>
[0401] The same operation as in the hydrogenation of the conjugated diene copolymer (4) was carried out except that the hydrogenation reaction time was changed to 0.15 hours.
[0402] The hydrogenated conjugated diene copolymer (20) obtained as above had a styrene content of 60% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 55%, and the hydrogenation rate was 11%.
[0403] <(Production Example 21): Hydrogenated conjugated diene copolymer (21)>
[0404] The same operation as in the hydrogenation of the conjugated diene copolymer (4) was carried out except that the hydrogenation reaction time was changed to 0.80 hours.
[0405] The hydrogenated conjugated diene copolymer (21) obtained as above had a styrene content of 60% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 55%, and the hydrogenation rate was 90%.
[0406] <(Production Example 22) Hydrogenated conjugated diene copolymer (22)>
[0407] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.
[0408] First, a cyclohexane solution (concentration: 20% by mass) containing 30 parts by mass of styrene and 70 parts by mass of butadiene was added.
[0409] Next, 1.94 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.35 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 20 minutes.
[0410] Methanol was then added to terminate the polymerization reaction, thereby obtaining a conjugated diene copolymer.
[0411] The conjugated diene copolymer obtained as above had a styrene content of 30% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, and the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 55%.
[0412] Using the obtained conjugated diene copolymer, 90 ppm of the hydrogenation catalyst prepared above was further added based on Ti per 100 parts by mass of the conjugated diene copolymer, and a hydrogenation reaction was carried out for about 0.5 hours under the conditions of a hydrogen pressure of 0.7 MPa and a temperature of 80°C to obtain a hydrogenated conjugated diene copolymer (22).
[0413] The hydrogenation rate of the obtained hydrogenated conjugated diene copolymer (22) was 50%.
[0414] <(Production Example 23) Hydrogenated conjugated diene copolymer (23)>
[0415] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.
[0416] First, a cyclohexane solution (concentration: 20% by mass) containing 70 parts by mass of styrene and 30 parts by mass of butadiene was added.
[0417] Next, 1.46 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.35 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 20 minutes.
[0418] Methanol was then added to terminate the polymerization reaction, thereby obtaining a conjugated diene copolymer.
[0419] The conjugated diene copolymer obtained as above had a styrene content of 70% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, and the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 55%.
[0420] Using the obtained conjugated diene copolymer, 90 ppm of the hydrogenation catalyst prepared above was further added based on Ti per 100 parts by mass of the conjugated diene copolymer, and a hydrogenation reaction was carried out for about 0.4 hours under the conditions of a hydrogen pressure of 0.7 MPa and a temperature of 80°C to obtain a hydrogenated conjugated diene copolymer (23).
[0421] The hydrogenation rate of the obtained hydrogenated conjugated diene copolymer (23) was 20%.
[0422] <(Production Example 24): Hydrogenated conjugated diene copolymer (24)>
[0423] The same operation as in the hydrogenation of the conjugated diene copolymer (23) was carried out except that the hydrogenation reaction time was changed to 0.70 hours.
[0424] The hydrogenated conjugated diene copolymer (24) obtained as above had a styrene content of 70% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 55%, and the hydrogenation rate was 80%.
[0425] <(Production Example 25): Hydrogenated conjugated diene copolymer (25)>
[0426] The same operation as in the hydrogenation of the conjugated diene copolymer (23) was carried out except that the hydrogenation reaction time was changed to 0.75 hours.
[0427] The hydrogenated conjugated diene copolymer (25) obtained as described above had a styrene content of 70% by mass and a weight average molecular weight of 0.5×104 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 56%, and the hydrogenation rate was 90%.
[0428] <(Production Example 26): Hydrogenated conjugated diene copolymer (26)>
[0429] The same operation as in the hydrogenation of the conjugated diene copolymer (23) was carried out except that the hydrogenation reaction time was changed to 0.15 hours.
[0430] The hydrogenated conjugated diene copolymer (26) obtained as above had a styrene content of 70% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond amount: unit (a) / butadiene) was 56%, and the hydrogenation rate was 10%.
[0431] <(Production Example 27): Hydrogenated conjugated diene copolymer (27)>
[0432] The same operation as in the hydrogenation of the conjugated diene copolymer (3) was carried out except that the hydrogenation reaction time was changed to 0.80 hours.
[0433] The hydrogenated conjugated diene copolymer (27) obtained as above had a styrene content of 40% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 55%, and the hydrogenation rate was 90%.
[0434] <(Production Example 28): Hydrogenated conjugated diene copolymer (28)>
[0435] The same operation as in the hydrogenation of the conjugated diene copolymer (3) was carried out except that the hydrogenation reaction time was changed to 0.15 hours.
[0436] The hydrogenated conjugated diene copolymer (28) obtained as above had a styrene content of 40% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond amount: unit (a) / butadiene) was 56%, and the hydrogenation rate was 9%.
[0437] <(Production Example 29): Hydrogenated conjugated diene copolymer (29)>
[0438] The same operation as in the hydrogenated conjugated diene copolymer (29) was carried out except that 0.49 parts by mass of n-butyl lithium was added based on 100 parts by mass of all monomers.
[0439] The hydrogenated conjugated diene copolymer (29) obtained as above had a styrene content of 60% by mass and a weight average molecular weight of 1.5×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 55%, and the hydrogenation rate was 50%.
[0440] <(Production Example 30): Hydrogenated conjugated diene copolymer (30)>
[0441] The same operation as in the hydrogenated conjugated diene copolymer (30) was carried out except that 0.26 parts by mass of n-butyl lithium was added based on 100 parts by mass of all monomers.
[0442] The hydrogenated conjugated diene copolymer (30) obtained as above had a styrene content of 60% by mass and a weight average molecular weight of 3.0×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 55%, and the hydrogenation rate was 55%.
[0443] <(Production Example 31): Hydrogenated conjugated diene copolymer (31)>
[0444] The same operation as in the hydrogenated conjugated diene copolymer (29) was carried out except that 0.60 mol of TMEDA was added to 1 mol of n-butyllithium and the polymerization temperature was set at 60°C.
[0445] The hydrogenated conjugated diene copolymer (31) obtained as above had a styrene content of 60% by mass and a weight average molecular weight of 1.5×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 76%, and the hydrogenation rate was 50%.
[0446] <(Production Example 32): Hydrogenated conjugated diene copolymer (32)>
[0447] The same operation as in the hydrogenation of the conjugated diene copolymer (29) was carried out except that 1.56 parts by mass of n-butyl lithium was added based on 100 parts by mass of the total monomers and the hydrogenation reaction time was set to 0.75 hours.
[0448] The hydrogenated conjugated diene copolymer (32) obtained as above had a styrene content of 60% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 54%, and the hydrogenation rate was 82%.
[0449] <(Production Example 33): Hydrogenated conjugated diene copolymer (33)>
[0450] The same operation as in the hydrogenation of the conjugated diene copolymer (32) was carried out except that the hydrogenation reaction time was changed to 0.20 hours.
[0451] The hydrogenated conjugated diene copolymer (33) obtained as described above had a styrene content of 60% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 55%, and the hydrogenation rate was 18%.
[0452] <(Production Example 34): Hydrogenated conjugated diene copolymer (34)>
[0453] The same operation as in the hydrogenation of the conjugated diene copolymer (24) was carried out except that the hydrogenation reaction time was changed to 0.50 hours.
[0454] The hydrogenated conjugated diene copolymer (34) obtained as above had a styrene content of 70% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond amount: unit (a) / butadiene) was 56%, and the hydrogenation rate was 55%.
[0455] <(Comparative Production Example 1): Conjugated Diene Copolymer (35)>
[0456] The same operation as in the conjugated diene copolymer (2) was carried out except that the hydrogenation reaction was not carried out.
[0457] The conjugated diene copolymer (35) obtained as described above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, and the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 54%.
[0458] <(Comparative Production Example 2) Hydrogenated conjugated diene copolymer (36)>
[0459] The same operation as in the hydrogenated conjugated diene copolymer (2) was carried out except that 0.21 parts by mass of n-butyl lithium was added based on 100 parts by mass of all monomers and 0.34 mol of TMEDA was added based on 1 mol of n-butyl lithium.
[0460] The hydrogenated conjugated diene copolymer (36) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 4.0×10 4 , molecular weight distribution was 1.10, the content of the unit (a) derived from 1,2-bond and / or 3,4-bond (vinyl bond amount: unit (a) / butadiene) was 55%, and the hydrogenation rate was 50%.
[0461] <(Comparative Production Example 3): Hydrogenated conjugated diene block copolymer (37)>
[0462] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.
[0463] First, a cyclohexane solution (concentration: 20% by mass) containing 10 parts by mass of styrene was added.
[0464] Next, 2.14 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.35 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 10 minutes.
[0465] Next, a cyclohexane solution (concentration: 20% by mass) containing 10 parts by mass of styrene and 80 parts by mass of butadiene was added, and polymerization was carried out at 70° C. for 30 minutes.
[0466] Methanol was then added to terminate the polymerization reaction, thereby obtaining a conjugated diene block copolymer.
[0467] The conjugated diene block copolymer (37) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, and the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 55%.
[0468] Using the obtained conjugated diene block copolymer, 90 ppm of the hydrogenation catalyst prepared above was further added based on Ti per 100 parts by mass of the conjugated diene block copolymer, and a hydrogenation reaction was carried out for about 0.5 hour under the conditions of a hydrogen pressure of 0.7 MPa and a temperature of 80°C to obtain a hydrogenated conjugated diene block copolymer (37).
[0469] The hydrogenation rate of the obtained hydrogenated conjugated diene block copolymer was 50%.
[0470] <(Comparative Production Example 4): Hydrogenated conjugated diene block copolymer (38)>
[0471] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.
[0472] First, a cyclohexane solution containing 20 parts by mass of butadiene (concentration: 20% by mass) was added.
[0473] Next, 2.14 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.35 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 10 minutes.
[0474] Next, a cyclohexane solution (concentration: 20% by mass) containing 20 parts by mass of styrene and 60 parts by mass of butadiene was added, and polymerization was carried out at 70° C. for 25 minutes.
[0475] Methanol was then added to terminate the polymerization reaction, thereby obtaining a conjugated diene block copolymer.
[0476] The conjugated diene block copolymer (38) obtained as above had a styrene content of 20% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, and the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 55%.
[0477] Using the obtained conjugated diene block copolymer, 90 ppm of the hydrogenation catalyst prepared above was further added based on Ti per 100 parts by mass of the conjugated diene block copolymer, and a hydrogenation reaction was carried out for about 0.5 hour under the conditions of a hydrogen pressure of 0.7 MPa and a temperature of 80°C to obtain a hydrogenated conjugated diene block copolymer (38).
[0478] The hydrogenation rate of the obtained hydrogenated conjugated diene block copolymer was 50%.
[0479] <(Comparative Production Example 5): Hydrogenated conjugated diene block copolymer (39)>
[0480] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.
[0481] First, a cyclohexane solution containing 20 parts by mass of styrene (concentration: 20% by mass) was added.
[0482] Next, 2.14 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.35 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 15 minutes.
[0483] Next, a cyclohexane solution containing 60 parts by mass of butadiene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 25 minutes.
[0484] Next, a cyclohexane solution containing 20 parts by mass of styrene (concentration: 20 mass%) was added, and polymerization was carried out at 70° C. for 15 minutes.
[0485] Methanol was then added to terminate the polymerization reaction, thereby obtaining a conjugated diene block copolymer.
[0486] The conjugated diene block copolymer (39) obtained as described above had a styrene content of 40% by mass and a weight average molecular weight of 0.5×10 4 , the molecular weight distribution was 1.10, and the content of the unit (a) derived from 1,2-bonding and / or 3,4-bonding (vinyl bond content: unit (a) / butadiene) was 55%.
[0487] Using the obtained conjugated diene block copolymer, 90 ppm of the hydrogenation catalyst prepared above was further added based on Ti per 100 parts by mass of the conjugated diene block copolymer, and a hydrogenation reaction was carried out for about 0.5 hour under the conditions of a hydrogen pressure of 0.7 MPa and a temperature of 80°C to obtain a hydrogenated conjugated diene block copolymer (39).
[0488] The hydrogenation rate of the obtained hydrogenated conjugated diene block copolymer was 50%.
[0489] In addition, SEPTON 8007 (manufactured by Kuraray Co., Ltd., weight average molecular weight: 83,000) was used as a hydrogenated conjugated diene-based copolymer.
[0490]
[0491] (Component (II): free radical initiator)
[0492] Perbutyl P-90 (manufactured by NOF Corporation)
[0493] Perbutyl C (manufactured by NOF Corporation)
[0494] Percumyl D (manufactured by NOF Corporation)
[0495] (Component (III): polar resin)
[0496] <Epoxy resin>
[0497] Bisphenol A type epoxy resin EXA-850CRP (manufactured by DIC Corporation)
[0498] <Polyimide resin>
[0499] Bis(3-ethyl-5-methyl-4-maleimidophenyl)methane (BMI-70) (manufactured by KI Chemicals Co., Ltd.)
[0500] 4,4'-Bismaleimide diphenylmethane (BMI-H) (manufactured by KI Chemicals Co., Ltd.)
[0501] <Polyphenylene ether resin (PPE resin)>
[0502] The polymerization of the PPE resin was carried out as follows.
[0503] A 1.5-liter jacketed reactor equipped with a nozzle for introducing oxygen-containing gas, a turbine stirring blade and a guide plate at the bottom of the reactor, and a reflux cooler at the exhaust line at the top of the reactor was used. 0.2512 g of cupric chloride dihydrate, 1.1062 g of 35% hydrochloric acid, 3.6179 g of di-n-butylamine, 9.5937 g of N,N,N',N'-tetramethylpropylenediamine, 211.63 g of methanol and 493.80 g of n-butanol, and 180.0 g of 2,6-dimethylphenol containing 5 mol% of 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane were added to the reactor. The composition mass ratio of the solvent used was n-butanol:methanol=70:30. Then, oxygen was introduced into the reactor at a rate of 180 mL / min using a nozzle while stirring vigorously, and a heat medium was circulated in the jacket to adjust the polymerization temperature so as to maintain 40°C. The polymerization liquid gradually presents a slurry state. When the polyphenylene ether reaches the desired number average molecular weight, stop the ventilation of the oxygen-containing gas and heat the obtained polymerization mixture to 50°C. Next, add hydroquinone (agent manufactured by Wako Pure Chemical Industries, Ltd.) in small amounts in batches, and continue to keep warm at 50°C until the slurry-like polyphenylene ether turns white. Next, add 720g of a methanol solution containing 6.5% by mass of 36% hydrochloric acid, filter, and further wash repeatedly with methanol to obtain wet polyphenylene ether. Next, vacuum dry at 100°C to obtain dry polyphenylene ether. ηsp / c is 0.103dl / g and the yield is 97%.
[0504] In the measurement of ηsp / c, the polyphenylene ether was prepared into a 0.5 g / dl chloroform solution, and the reduced viscosity (ηsp / c) at 30° C. was determined using an Ubbelohde viscometer. The unit is dl / g.
[0505] The obtained polyphenylene ether was modified as follows.
[0506] 152.5 g of polyphenylene ether and 152.5 g of toluene are mixed and heated to about 85°C. Next, 2.1 g of dimethylaminopyridine is added. When all the solids are dissolved, 18.28 g of methacrylic anhydride is slowly added. The obtained solution is continuously mixed while being maintained at 85°C for 3 hours. Next, the solution is cooled to room temperature to obtain a toluene solution of methacrylate-terminated polyphenylene ether. For the obtained toluene solution, 1000 mL of methanol at 10°C is added dropwise in small amounts in a cylindrical 3L SUS container equipped with a homogenizer for stirring. The obtained powder is filtered, washed with methanol, and dried at 85°C under nitrogen for 18 hours.
[0507] <Phenoxy resin>
[0508] YP-50S (manufactured by Nippon Steel Chemical Co., Ltd.)
[0509] (Component (IV): curing agent)
[0510] Cyanate curing agent 2,2-bis(4-cyanatephenyl)propane (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0511] Diamine curing agent 4,4'-diaminodiphenylmethane (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0512] 1-Benzyl-2-phenylimidazole (Tokyo Chemical Industry Co., Ltd.)
[0513] Phenolic curing agent KA-1163 (manufactured by DIC Corporation)
[0514] Triallyl isocyanurate (TAIC TM )(Made by Mitsubishi Chemical Corporation)
[0515] [Method for measuring physical properties of resin composition]
[0516] ((1) Dielectric loss tangent and dielectric constant)
[0517] The dielectric loss tangent at 10 GHz was measured using the cavity resonance method.
[0518] As measuring devices, a network analyzer (N5230A, manufactured by Agilent Technologies) and a cavity resonator (Cavity Resornator CP series) manufactured by Kanto Denshi Application Development Co., Ltd. were used.
[0519] Regarding the measurement sample, a test piece of 2.6 mm in width×80 mm in length was cut out from a cured film described later, and this was used as the measurement sample.
[0520] Using the dielectric loss tangent and dielectric constant obtained above, the following examples and comparative examples were evaluated according to the following criteria.
[0521] <Evaluation Criteria in (Examples 1 to 42) and (Comparative Examples 1 to 13)>
[0522] Evaluation was performed using the difference in dielectric loss tangent and dielectric constant between Comparative Example 1 not including the conjugated diene-based copolymer and each of the Examples or Comparative Examples (Comparative Example 1 - each of the Examples or Comparative Examples).
[0523] Dielectric loss tangent
[0524] ◎: 0.013 or more
[0525] ○: 0.010 or more, less than 0.013
[0526] △: 0.008 or more, less than 0.010
[0527] ×: less than 0.008 (including equal value and negative difference)
[0528] Dielectric constant
[0529] ◎:0.41 or more
[0530] ○: 0.38 or more, less than 0.41
[0531] △: 0.30 or more, less than 0.38
[0532] ×: less than 0.30 (including equal value and negative difference)
[0533] <Evaluation Criteria in (Examples 43 to 58) and (Comparative Examples 14 to 25)>
[0534] Evaluation was performed using the difference in dielectric loss tangent and dielectric constant between Comparative Example 14 not including the conjugated diene-based copolymer and each of the Examples or Comparative Examples (Comparative Example 14-each of the Examples or Comparative Examples).
[0535] Dielectric loss tangent
[0536] ◎:0.0013 or more
[0537] ○: 0.0011 or more, less than 0.0013
[0538] △: 0.0008 or more, less than 0.0011
[0539] ×: Less than 0.0008 (including equal values and negative differences)
[0540] Dielectric constant
[0541] ◎:0.16 or above
[0542] ○: 0.14 or more, less than 0.16
[0543] △: 0.10 or more, less than 0.14
[0544] ×: less than 0.10 (including equal value and negative difference)
[0545] <Evaluation Criteria in (Examples 59 to 69) and (Comparative Examples 26 to 38)>
[0546] Evaluation was performed using the difference in dielectric loss tangent and dielectric constant between Comparative Example 26 not containing a conjugated diene-based copolymer and each of the Examples and Comparative Examples (Comparative Example 26-each of the Examples or Comparative Examples).
[0547] Dielectric loss tangent
[0548] ◎:0.0013 or more
[0549] ○: 0.0011 or more, less than 0.0013
[0550] △: 0.0008 or more, less than 0.0011
[0551] ×: Less than 0.0008 (including equal values and negative differences)
[0552] Dielectric constant
[0553] ◎:0.13 or above
[0554] ○: 0.11 or more, less than 0.13
[0555] △: 0.08 or more, less than 0.11
[0556] ×: less than 0.08 (including equal value and negative difference)
[0557] ((2) Strength (tensile strength), toughness (elongation at break))
[0558] A sheet of a cured product composed of the resin composition described below was punched into a JIS No. 1 dumbbell shape and subjected to a tensile test at room temperature at a tensile speed of 1 mm / min to calculate the tensile strength (MPa) and elongation at break (mm).
[0559] The tensile strength and elongation at break obtained above were used to evaluate the following Examples and Comparative Examples according to the following criteria.
[0560] <Evaluation Criteria in (Examples 1 to 42) and (Comparative Examples 1 to 13)>
[0561] Evaluation was performed using the ratio of tensile strength and elongation at break between Comparative Example 1 not containing a conjugated diene copolymer and each Example or Comparative Example (each Example or Comparative Example / Comparative Example 1).
[0562] Tensile Strength
[0563] ◎: 1.1 times or more
[0564] ○: 0.8 times or more, less than 1.1 times
[0565] △: 0.5 times or more, less than 0.8 times
[0566] ×: less than 0.5 times
[0567] Elongation at break
[0568] ◎: 2.5 times or more
[0569] ○: 2.0 times or more, less than 2.5 times
[0570] △: 1.0 times or more, less than 2.0 times
[0571] ×: less than 1.0 times
[0572] <Evaluation Criteria in (Examples 43 to 58) and (Comparative Examples 14 to 25)>
[0573] Evaluation was performed by the ratio of the tensile strength and the elongation at break between Comparative Example 14 not containing a conjugated diene copolymer and each Example or Comparative Example (each Example or Comparative Example / Comparative Example 14).
[0574] Tensile Strength
[0575] ◎: 1.1 times or more
[0576] ○: 0.8 times or more, less than 1.1 times
[0577] △: 0.5 times or more, less than 0.8 times
[0578] ×: less than 0.5 times
[0579] Elongation at break
[0580] ◎: 2.5 times or more
[0581] ○: 2.0 times or more, less than 2.5 times
[0582] △: 1.0 times or more, less than 2.0 times
[0583] ×: less than 1.0 times
[0584] <Evaluation Criteria in (Examples 59 to 69) and (Comparative Examples 26 to 38)>
[0585] Evaluation was performed using the ratio of the tensile strength and elongation at break between Comparative Example 26 not containing a conjugated diene copolymer and each Example or Comparative Example (each Example or Comparative Example / Comparative Example 26).
[0586] Tensile Strength
[0587] ◎: 1.1 times or more
[0588] ○: 0.8 times or more, less than 1.1 times
[0589] △: 0.5 times or more, less than 0.8 times
[0590] ×: less than 0.5 times
[0591] Elongation at break
[0592] ◎: 1.5 times or more
[0593] ○: 1.0 times or more, less than 1.5 times
[0594] △: 0.8 times or more, less than 1.0 times
[0595] ×: less than 0.8 times
[0596] ((3) Storage stability)
[0597] The varnishes of Examples and Comparative Examples described below were left to stand at 30°C / 50%RH, and the state at that time was observed. The number of days until layer separation and / or precipitation of gel-like components occurred and the presence or absence of the same were evaluated according to the following criteria.
[0598] ◎: More than 120 days (including no precipitation)
[0599] ○: 90 days or more
[0600] △: More than 30 days
[0601] ×: Less than 30 days
[0602] [Preparation of resin composition]
[0603] (Examples 1 to 42), (Comparative Examples 1 to 13)
[0604] The component ratios and physical properties are shown in Tables 4 to 7 below.
[0605] First, components other than the phenolic curing agent and the phenoxy resin are added to toluene, stirred, and dissolved to prepare a varnish having a concentration of 20% by mass to 50% by mass.
[0606] A phenolic curing agent solution having a concentration of 50% by mass was prepared using methyl ethyl ketone (special grade product manufactured by Wako Pure Chemical Industries, Ltd.) as a solvent, and added to the varnish and stirred to prepare a varnish.
[0607] A phenoxy resin solution having a concentration of 25% by mass was prepared using cyclohexanone (special grade product manufactured by Wako Pure Chemical Industries, Ltd.) as a solvent, and the solution was added to the varnish and stirred to prepare a varnish.
[0608] The varnish was applied onto a release-treated KAPTON film at a rate of 30 mm / sec, and then dried at 100°C for 30 minutes using a blow dryer under a nitrogen stream to obtain a film.
[0609] The obtained film was subjected to a curing reaction at 200° C. for 90 minutes using a blower dryer under a nitrogen stream to obtain a cured film.
[0610] The cured product film was provided as an evaluation sample.
[0611] (Examples 43 to 58), (Comparative Examples 14 to 25)
[0612] First, a polyimide resin as a polar resin and a cyanate curing agent and / or a diamine curing agent were dissolved at 160° C. in the mixing ratios shown in Tables 8 and 9 below, and reacted for 6 hours under stirring to obtain a bismaleimide-triazine resin oligomer.
[0613] The obtained bismaleimide-triazine resin oligomer is dissolved in toluene, and the remaining components are added, stirred, and dissolved to prepare a varnish having a concentration of 20% by mass to 50% by mass.
[0614] The above varnish was applied onto a release-treated KAPTON film at a speed of 30 mm / sec.
[0615] Thereafter, the film was dried at 100° C. for 30 minutes using a blower dryer under a nitrogen stream to obtain a film.
[0616] The film was subjected to a curing reaction at 200° C. for a maximum of 90 minutes using a blower dryer under a nitrogen stream to obtain a cured film.
[0617] The cured product film was provided as an evaluation sample.
[0618] (Examples 59 to 69), (Comparative Examples 26 to 38)
[0619] The component ratios and physical properties are shown in Tables 10 and 11 below.
[0620] First, each component is added to toluene (special grade product manufactured by Wako Pure Chemical Industries, Ltd. is used as it is), stirred, and dissolved to prepare a varnish having a concentration of 20% by mass to 50% by mass.
[0621] The varnish was applied to a release treated KAPTON film at a speed of 30 mm / sec, and then dried in a blow dryer at 100°C for 30 minutes under a nitrogen stream to obtain a film. The obtained film was cured in a blow dryer at 200°C for 90 minutes under a nitrogen stream to obtain a cured film.
[0622] The cured product film was provided as an evaluation sample.
[0623] This shows that the cured product using the hydrogenated conjugated diene copolymer of the example has an excellent balance between dielectric properties and strength. It is also known that the cured product of the present invention is suitable for use in printed wiring boards using glass cloth or metal laminates.
[0624]
[0625]
[0626]
[0627]
[0628]
[0629]
[0630]
[0631]
[0632] This application is based on the Japanese patent application (Japanese Patent Application No. 2022-081444) filed with the Japan Patent Office on May 18, 2022, the contents of which are incorporated into this specification as a reference.
[0633] Industrial Applicability
[0634] The hydrogenated conjugated diene copolymer, resin composition and cured product of the present invention have industrial applicability as materials for films, prepregs, electronic circuit boards and next-generation communication boards.
Claims
1. A hydrogenated conjugated diene copolymer, wherein: The copolymer is a random copolymer having vinyl aromatic monomer units and conjugated diene monomer units. The random copolymer is hydrogenated, The weight average molecular weight of the random copolymer is 35,000 or less.
2. The hydrogenated conjugated diene copolymer according to claim 1, wherein The hydrogenation rate of the hydrogenated conjugated diene copolymer is 5% to 95%.
3. The hydrogenated conjugated diene copolymer according to claim 1, wherein The conjugated diene copolymer before hydrogenation of the hydrogenated conjugated diene copolymer comprises a unit (a) derived from a 1,2-bond and / or a 3,4-bond, and a unit (b) derived from a 1,4-bond, When the total content of the conjugated diene monomer units is 100%, the content of the units (a) derived from 1,2-bonds and / or 3,4-bonds is 80% or less.
4. The hydrogenated conjugated diene copolymer according to claim 2, wherein The conjugated diene copolymer before hydrogenation of the hydrogenated conjugated diene copolymer comprises a unit (a) derived from a 1,2-bond and / or a 3,4-bond, and a unit (b) derived from a 1,4-bond, When the total content of the conjugated diene monomer units is 100%, the content of the units (a) derived from 1,2-bonds and / or 3,4-bonds is 80% or less.
5. The hydrogenated conjugated diene copolymer according to claim 1, wherein The hydrogenation rate of the hydrogenated conjugated diene copolymer is 15% to 85%.
6. The hydrogenated conjugated diene copolymer according to claim 1, wherein The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene copolymer is 35% by mass to 75% by mass.
7. A resin composition comprising: Component (I): the hydrogenated conjugated diene copolymer according to any one of claims 1 to 6; and at least one component selected from the group consisting of the following components (II) to (IV), Component (II): free radical initiator; Component (III): polar resin, which does not include component (I); Component (IV): a curing agent, excluding component (II).
8. The resin composition according to claim 7, wherein The resin composition contains the component (III), The component (III) is at least one selected from the group consisting of epoxy resins, polyimide resins, polyphenylene ether resins, liquid crystal polyester resins, and fluorine resins.
9. The resin composition according to claim 7, wherein The component (III) is at least one polar resin selected from the group consisting of epoxy resin, polyimide resin and polyphenylene ether resin. The component (I) is the hydrogenated conjugated diene copolymer according to claim 6.
10. The resin composition according to claim 8, wherein The component (III) is an epoxy resin. 11 . A cured product comprising the conjugated diene copolymer according to claim 1 . 12 . A cured product, which is a cured product of the resin composition according to claim 7 . 13 . A resin film comprising the resin composition according to claim 7 . 14 . A prepreg which is a composite of a substrate and the resin composition according to claim 7 .
15. The prepreg according to claim 14, wherein The substrate is glass cloth. 16 . A laminate comprising the resin film according to claim 13 and a metal foil. 17 . A laminate comprising a cured product of the prepreg according to claim 14 and a metal foil.
18. A printed wiring board comprising the cured product according to claim 12.
Citation Information
Patent Citations
Olefinic polymerisation using silylether initiators
GB2241239A
JP1988004841B2
Olefin hydrogenation catalyst and hydrogenation of polymer using said catalyst
JP1989037970B2
Method for hydrogenating olefin
JP1989053851B2
JP1990009041B2
